Controllable self-annealing microgel particles for biomedical applications

The interconnected pore microgel scaffold, manufactured through microfluidic technology, solves the problem of batch variation and degradation rate limits of existing wound treatment materials, achieves rapid tissue regeneration and structural support, and improves wound healing efficiency.

JP7627498B2Active Publication Date: 2025-02-06RGT UNIV OF CALIFORNIA
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2022134723
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2015-01-13
Filing Date
2022-08-26
Publication Date
2025-02-06
Estimated Expiration
2035-07-17

AI Technical Summary

Technical Problem

Existing wound treatment materials have batch variation and degradation rates limitations that cannot effectively support tissue growth, and traditional methods cannot provide optimal scaffolding structures to promote new tissue growth, resulting in extended healing time.

Method used

Microgel particles are used to form injectable micropore synthetic hydrogels, and uniform microgel balls are made through microfluidic molding technology to form micropore synthetic hydrogel scaffold with interconnected pore structures, promoting cell migration and tissue regeneration.

Benefits of technology

Rapid tissue regeneration and structural support are achieved, reducing scar formation, improving wound healing efficiency, and avoiding the adverse effects of material degradation on the tissue.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007627498000001
    Figure 0007627498000001
  • Figure 0007627498000002
    Figure 0007627498000002
  • Figure 0007627498000003
    Figure 0007627498000003
Patent Text Reader

Abstract

Systems, compositions, methods, and devices are provided that provide biomaterials that promote rapid tissue regeneration while maintaining structural support for the tissue surrounding the wound. [Solution] A microporous gel system is provided, comprising an aqueous solution containing a plurality of microgel particles comprising a biodegradable crosslinker. In some aspects, the microgel particles act as gel building blocks that anneal to one another to form a scaffold composed of covalently stabilized microgel particles with internal voids. In some aspects, annealing of the microgel particles occurs after exposure to an annealing agent, either endogenously present or exogenously added. In some embodiments, annealing of the microgel particles requires the presence of an initiator, such as exposure to light. In certain embodiments, tuning the chemical and physical properties of the gel building blocks can allow for downstream control of the resulting assembled scaffold.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Related Applications This application claims priority to U.S. Provisional Patent Application No. 62 / 025,844, filed July 17, 2014, No. 62 / 059,463, filed October 3, 2014, and No. 62 / 103,002, filed January 13, 2015. Priority is claimed under 35 U.S.C. § 119. The above patent applications are incorporated by reference as if fully set forth herein.

[0002] The technical field relates generally to the field of wound care, and in particular to the use of microgel particles and scaffolds comprising said particles to treat and seal wounds, and for tissue filler applications. [Background technology]

[0003] A central concept related to tissue development and regeneration is collective cell migration, a process in which the simultaneous migration of an entire cellular network to a developing area promotes the formation of functional tissue. Researchers have made efforts to discover wound would-healing agents; however, these materials exhibit batch-to-batch variability and degradation rates that limit the extension of structural support to the growing tissue. Synthetic materials are more tunable than natural materials, and their mechanical properties have been engineered for use with a wide range of tissue types. However, despite this tunability, injectable synthetic biomaterials have been limited to non-porous or nano-porous scaffolds that require physical degradation for cell migration through the material. Porous synthetic hydrogels containing preformed, micro-scale, interconnected pores allow greater cell mobility without the need for degradation, avoiding the trade-off between cell mobility and material stability inherent in non-porous scaffolds. Typical pore formation modes include toxic porogen removal, or degradation of encapsulated microparticles, which require these constructs to be molded ex vivo, as injectable biomaterials do, preventing them from seamlessly integrating with the surrounding tissue, or require prolonged in vivo development to degrade the porous structure. For example, Healionics Corporation has developed a technology called Sphere Templated Anigiogenic Regeneration (STAR), which involves sintering a series of uniformly sized packed beads, casting a polymer into the interstices between the beads, and dissolving the beads to obtain a pore network of interconnected spherical voids, thereby forming a STAR scaffold. However, as mentioned above, these conventional methods require toxic porogen removal. Summary of the Invention

[0004] Human skin wounds are an ever-growing threat to public health and the economy, and are very difficult to treat. Because dry wounds heal much slower than wet wounds, physicians strive to keep the area moist when treating skin wounds. To accomplish this, physicians often use ointments to seal the wound, much like filling a hole in a road with new asphalt. However, these and other traditional approaches to wound healing fail to provide an optimal scaffolding to allow new tissue growth. As a result, new tissue growth, if at all, is relatively slow and fragile, resulting in longer healing times, to the extent that timely healing is possible.

[0005] In the context of artificial tissue healing, the inventors have identified the gold standard of developing interconnected microporous scaffolds that allow interconnected cell networks and collective migration without the need for scaffold degradation. Otherwise, invasive procedures for implantation are essential for bulk integration with surrounding tissue. In fact, to be most effective, the inventors have identified that these materials should promote collective cell migration to mediate regeneration while providing molecular cues that promote wound healing and niche recognition. Furthermore, the inventors have also identified that these materials should be seamlessly replaceable with migratory cells and natural parent tissue, be able to provide stable structural support prior to replacement, be easily delivered, and be able to conform to the injury site to minimize fibrotic and inflammatory responses.

[0006] Provided herein are systems, compositions, methods, and devices that implement these principles and provide biomaterials that promote rapid tissue regeneration while maintaining structural support for tissue surrounding a wound. Indeed, the inventors have solved a long-standing unmet medical need in the field of tissue engineering by using tailored material chemistry based on flowable or injectable microgels and micro fluidic fabrication of uniform spherical building blocks, including building blocks the width of a human hair.

[0007] The technology described herein uses chemistry to create small microgels that can be assembled into larger units while leaving pathways for cell infiltration. The result is packed clusters of microscopic synthetic polymer bodies (e.g., spheres) that adhere to each other's surfaces, similar to gumball jars stuck together. The clusters create a microporous annealed particulate scaffold (e.g., a porous gel scaffold) that seals the wound. New tissue rapidly grows into the voids between the microgel particles, and the microgel particles degrade into the body, leaving a matrix of newly grown tissue where the wound once was. New tissue continues to grow until the wound is completely healed.

[0008] The microgel systems described herein are a substantial improvement over previous products. For example, the techniques described herein do not require the addition of growth factors to attract cells to the material. The topology of the microgel network encourages cell migration into the microgel.

[0009] The inventors have shown that the microgels can promote new cell growth and the formation of connected cellular networks at rates not seen before: for example, during in vivo studies, significant tissue regeneration was observed within the first 48 hours, resulting in more healing over a 5-day period compared to conventional materials used today.

[0010] The technology described herein is useful in a wide range of applications. For example, the microgel technology can be used in wound applications, including acute injuries such as lacerations and surgical wound closure, as well as more long-term applications such as diabetic ulcers and large area burns. The hydrogel scaffolds described herein may also be useful in trauma situations, such as in war zones or emergency rooms.

[0011] In one embodiment, systems, compositions, methods, and devices are described herein that include a microporous gel that includes an aqueous solution containing a plurality of microgel particles and a crosslinker (e.g., a biodegradable crosslinker). The microporous gels described herein are flowable and / or injectable and can be applied in a number of different ways, for example, topically or by injection. The injected and / or flowable microporous gels can be inserted percutaneously or into deep tissues. The flowable microporous gels can also be administered topically to the dermis and other tissues.

[0012] In one aspect, when the annealing agent is applied to a plurality of microgel particles, the microgel particles form a scaffold of covalently stabilized microgel particles with internal voids. In certain applications, the systems, compositions, methods, and devices are specifically designed for biomedical applications. In some embodiments, the microporous gel particles further comprise a crosslinking agent, including a matrix metalloproteinase (MMP)-degradable crosslinking agent. In one or more embodiments, the annealing agent comprises activated factor XIIIa. In further or additional embodiments, the annealing agent comprises eosin Y, a free radical transfer agent, or a combination thereof.

[0013] In some embodiments, the microgel systems, compositions, methods, and devices further comprise a light source configured to irradiate the mixture of a plurality of microgel particles and an annealing agent. In one or more embodiments, the microporous gel particles comprise a cell adhesive peptide exposed on a surface thereof. In some embodiments, the microporous gel particles comprise a K-peptide. In further or additional embodiments, the microporous gel particles comprise a K-peptide comprising a lysine group recognized by activated factor XIIIa. In some embodiments, the microporous gel particles comprise a Q-peptide. In some embodiments, the Q-peptide comprises a glutamine group recognized by activated factor XIIIa. In some embodiments, the microporous gel particles comprise a crosslinker that is degradable. In some embodiments, the microporous gel particles comprise gaps comprising an interface that exhibits a negative concavity. In one or more embodiments, the covalently stabilized scaffold of microgel particles has a void volume of about 10% to about 50%.

[0014] In one embodiment, a microporous gel system for biomedical applications includes an aqueous solution containing a plurality of microgel particles formed using a biodegradable crosslinker, such as a matrix metalloproteinase (MMP)-degradable crosslinker, and an annealing agent that, when applied to the plurality of microgel particles, causes the microgel particles to form a scaffold composed of covalently stabilized microgel particles having internal voids.

[0015] In another embodiment, the microporous gel system comprises a delivery device and a collection of biodegradable microgel particles contained in an aqueous solution and stored within the delivery device. An annealing agent or annealing agent precursor is also stored within the delivery device. The delivery device may contain a single or multiple compartments depending on the particular embodiment employed.

[0016] In another embodiment, a method of treating tissue includes delivering to the tissue an aqueous solution containing a plurality of microgel particles decorated with cell adhesion peptides, the microgel particles being formed using a biodegradable crosslinker, such as a matrix metalloproteinase (MMP)-degradable crosslinker, and exposing the plurality of microgel particles to an annealing agent that anneals the microgel particles to form a scaffold composed of covalently stabilized microgel particles having internal voids.

[0017] In another embodiment, a microporous gel system for biomedical applications comprises a collection of microgel particles formed by reaction of a backbone polymer with one or more cell adhesive moieties, one or more annealing moieties, and a biodegradable network crosslinker moiety. The microporous gel system includes an endogenous or exogenous annealing agent that connects the microgel particles in situ via the annealing moiety to form a scaffold of covalently stabilized microgel particles with internal voids.

[0018] In another aspect, systems, compositions, methods, and devices comprising a delivery device or delivery mechanism and a microporous gel are described herein. In some embodiments, the delivery device contains an aqueous solution containing a plurality of microgel particles and an annealing agent or an annealing agent precursor. In one or more embodiments, the delivery device comprises a single compartment delivery device containing an aqueous solution containing a plurality of microgel particles and an annealing agent. In one or more embodiments, the delivery device comprises a multiple (e.g., dual) compartment delivery device, one compartment contains an aqueous solution containing a plurality of microgel particles and a first annealing agent precursor, and a second compartment contains an aqueous solution containing a plurality of microgel particles and a second annealing agent precursor. In some embodiments, the microporous gel further comprises a (MMP)-degradable crosslinker comprising at least one D-amino acid. In further or additional embodiments, the microgel particles comprise a (MMP)-degradable crosslinker comprising a plurality of D-amino acids.

[0019] In yet another aspect, a microporous gel system is described herein that includes a delivery device; a plurality of biodegradable microgel particles contained in an aqueous solution and stored in the delivery device; and an annealing agent or annealing agent precursor stored in the delivery device. In one or more embodiments, the microporous gel particles further include a collection of two or more biodegradable microgel particles contained in an aqueous solution and stored in the delivery device. In an embodiment, the delivery device includes two compartments, the biodegradable microgel particles are stored in each of the two compartments, a first annealing precursor is stored in one compartment, a second annealing precursor is stored in the other compartment, and the annealing agent is formed by the presence of both the first annealing precursor and the second annealing precursor. In one or more embodiments, the delivery device includes a single compartment, and the collection of biodegradable microgel particles and the annealing agent are both stored in the single compartment. In further or additional embodiments, the annealing agent includes a photoinitiator and a free radical transfer agent stored in the single compartment. In further or additional embodiments, the microporous gel system further comprises a light emitting device configured to irradiate the mixture of the collection of biodegradable microgel particles and the annealing agent. In certain embodiments, the microgel particles comprise substantially monodisperse spheres. In one or more embodiments, the substantially monodisperse spheres have diameters in the range of about 30 micrometers to about 150 micrometers. In further or additional embodiments, the microgel particles are covalently linked to each other after annealing.

[0020] In another aspect, a method of treating tissue is provided that includes delivering an aqueous solution containing a plurality of microgel particles to the tissue; and exposing the plurality of microgel particles to an annealing agent that anneals the microgel particles to form a scaffold of covalently stabilized microgel particles having internal voids. In some embodiments, the plurality of microgel particles are decorated with cell adhesion peptides, and the microgel particles are formed using a matrix metalloproteinase (MMP)-degradable crosslinker. In one or more embodiments, the annealing agent is delivered to the tissue. In some embodiments, the annealing agent is present within the tissue. In still additional embodiments, the method further includes initiating annealing of the microgel particles by exposure to light. In some embodiments, the wavelength of the light is in the visible range. In some embodiments, the wavelength of the light is in the infrared range. In one or more embodiments, the aqueous solution and the annealing agent are delivered simultaneously. In some embodiments, the aqueous solution and the annealing agent are delivered sequentially. In further or additional embodiments, the microgel particles include a therapeutically active chemical. In some embodiments, the microgel particles expose or elute the chemical to the tissue. In one or more embodiments, the tissue comprises a site of cosmetic reconstruction, chronic wound development, acute tissue injury, or a tissue gap created by a surgical incision. In yet additional embodiments, the (MMP)-degradable crosslinker comprises a D-amino acid.

[0021] In another aspect, a microporous gel system or device is provided that includes an assembly of microgel particles comprising a backbone polymer having one or more cell adhesive moieties, one or more annealing moieties, and one or more biodegradable network crosslinker moieties; and an endogenous or exogenous annealing agent that connects the microgel particles in situ via the annealing moieties to form a scaffold of covalently stabilized microgel particles having internal voids. In some embodiments, the backbone polymer comprises poly(ethylene glycol)vinylsulfone. In one or more embodiments, the one or more cell adhesive moieties comprise an RGD peptide or a fragment thereof, a fibronectin or a fragment thereof, a collagen or a fragment thereof, or a laminin or a fragment thereof. In some embodiments, the one or more cell adhesive moieties comprise an RGD peptide or a fragment thereof. In one embodiment, the one or more cell adhesive moieties comprise SEQ ID NO:3 or a fragment thereof. In further or additional embodiments, the one or more annealing moieties comprise a K-peptide and a Q-peptide. In some embodiments, the K-peptide comprises a lysine group recognized by activated factor XIIIa, and the Q-peptide comprises a glutamine group recognized by activated factor XIIIa. In some embodiments, the biodegradable network crosslinker component comprises a matrix metalloprotease (MMP)-degradable crosslinker. In one or more embodiments, the (MMP)-degradable crosslinker comprises D-amino acids. In some embodiments, the population of microgel particles comprises two or more types of microgel particles. In one or more embodiments, a first type of microgel particles comprises an (MMP)-degradable crosslinker that comprises D-amino acids, and a second type of microgel particles comprises an (MMP)-degradable crosslinker that comprises only L-amino acids. In one or more embodiments, the system or device comprises a single compartment delivery device containing the population of microgel particles and an annealing agent.In one or more embodiments, the system or device further comprises a dual compartment delivery device, one compartment containing an aqueous solution containing a plurality of microgel particles and a first annealing agent precursor, and a second compartment containing an aqueous solution containing a plurality of microgel particles and a second annealing agent precursor, wherein the annealing agent is formed by the presence of the first annealing agent precursor and the second annealing agent precursor.

[0022] In a further aspect, a method of treating tissue is described that includes delivering to the tissue a first layer of microgel particles decorated with cell adhesive peptides, where the microgel particles are formed with a biodegradable crosslinker; exposing the first layer to an annealing agent that anneals the microgel particles to form a scaffold of covalently stabilized microgel particles having internal voids; delivering to the tissue a second layer of microgel particles decorated with cell adhesive peptides, where the microgel particles are formed with a biodegradable crosslinker, where the microgel particles in the second layer differ in one of physical properties or chemical composition compared to the microgel particles in the first layer; and exposing the second layer to an annealing agent that anneals the microgel particles to form a scaffold of covalently stabilized microgel particles having internal voids. In one or more embodiments, the microgel particles in the second layer have a different size. In yet additional embodiments, the microgel particles in the second layer have a different shape. In one or more embodiments, the microgel particles in the second layer have a different stiffness. In certain embodiments, the microgel particles in the second layer have a different chemical moiety than the chemical moiety in the first layer. In further or additional embodiments, the microgel particles in the second layer have a different concentration of a chemical moiety than the same chemical moiety in the first layer.

[0023] In another aspect, a method of treating tissue is provided that includes delivering to the tissue an aqueous solution containing a plurality of microgel particles decorated with cell adhesive peptides, where the microgel particles are formed using a biodegradable crosslinking agent; and exposing the plurality of microgel particles to an annealing agent that anneals the microgel particles to form a scaffold composed of covalently stabilized microgel particles having internal voids.

[0024] In another embodiment, a method of treating tissue includes delivering a first layer of cell adhesive peptide-decorated microgel particles to the tissue, the microgel particles formed with a biodegradable crosslinker. The first layer is exposed to an annealing agent that anneals the microgel particles to form a scaffold of covalently stabilized microgel particles having internal voids. A second layer of cell adhesive peptide-decorated microgel particles is delivered to the tissue, the microgel particles formed with a biodegradable crosslinker, the microgel particles in the second layer differing in either physical properties or chemical composition as compared to the microgel particles in the first layer. The second layer is exposed to an annealing agent that anneals the microgel particles to form a scaffold of covalently stabilized microgel particles having internal voids.

[0025] In another embodiment, a method of treating tissue includes delivering to the tissue an aqueous solution containing a plurality of microgel particles decorated with cell adhesive peptides, the microgel particles being formed using a biodegradable crosslinking agent, and exposing the plurality of microgel particles to an annealing agent that anneals the microgel particles to form a scaffold comprised of covalently stabilized microgel particles having internal voids.

[0026] In yet an additional aspect, a method of making microgel particles is described that includes providing a microfluidic device for generating water-in-oil droplets having a plurality of input channels leading to a common channel and a pair of oil-pinching channels intersecting the common channel at a downstream location; flowing a second solution containing a biodegradable crosslinker into the second input channel; flowing oil and a surfactant into the pair of oil-pinching channels to form droplets containing a first prepolymer solution and a second solution; and collecting microgel particles formed by crosslinking of the droplets. In another embodiment, the method further includes a third input channel interposed between the first and second input channels, and a third inert solution containing a prepolymer is flowed into the third input channel. In one or more embodiments, the method further comprises sheathing the generated droplets with an additional sheathing channel pair located downstream of where the oil constriction channel pair crosses the common channel, the additional sheathing channel pair having a higher concentration of oil and surfactant than the surfactant contained upstream of the oil constriction channel pair. In one embodiment, the method further comprises centrifuging the collected microgel particles. In another aspect, the method comprises reducing the free water volume content of the centrifuged microgel particles. In one or more embodiments, the method comprises storing the collected microgel particles for an extended period of time (e.g., months to years).

[0027] In yet another embodiment, a method of making microgel particles includes providing a water-in-oil droplet generating microfluidic device having multiple input channels leading to a common channel and a pair of oil constriction channels intersecting the common channel at a downstream location. A first prepolymer solution containing an oligopeptide modified polymer backbone is flowed into the first input channel. A second solution containing a biodegradable crosslinker is flowed into the second input channel. Oil and a surfactant are flowed into the pair of oil constriction channels to form droplets containing the first prepolymer solution and the second solution. Microgel particles are formed by crosslinking of the droplets and are then collected.

[0028] Other objects, features and advantages of the present disclosure will become apparent to those skilled in the art from the following detailed description. However, it should be understood that the detailed description and specific examples, while illustrating some embodiments of the present disclosure, are given for illustration and not for limitation. Many modifications and changes within the scope of the present disclosure can be made without departing from the spirit thereof. The present disclosure includes all such modifications. Furthermore, aspects of one embodiment can be utilized in other different embodiments. [Brief description of the drawings]

[0029] The novel features of the present disclosure are set forth with particularity in the appended claims. A better understanding of the features and advantages of the present disclosure can be obtained by reference to the following detailed description that sets forth illustrative embodiments, in which the principles of the disclosure are utilized, and the accompanying drawings, in which: [Figure 1] FIG. 1 illustrates a portion of a scaffold formed from a number of annealed microgel particles. [Diagram 2] FIG 2A illustrates an exemplary method of injecting microgel particles into a wound site to heal the wound site. FIG 2B illustrates a schematic of an exemplary annealing reaction between different microgel particles facilitated by linkers on the microgel particle surface. FIG 2C illustrates an exemplary process of tissue infiltration into a scaffold formed within a delivery site on the tissue, where the boundary between the tissue and the microgel represents any contact between them, and cells can pass through said contact while migrating inward from the tissue or outward from the microgel toward the tissue. [Diagram 3]FIG. 3A shows a top view of a microfluidic device according to an embodiment used to create multiple microgel particles as part of a microporous gel system. FIG. 3B shows a close-up of the droplet generation region and the downstream oil / surfactant constriction region (see boxed area in FIG. 3A). FIG. 3C shows a close-up perspective view of the two branching channels illustrated in FIG. 3A. FIG. 3D shows a side view of the microfluidic device of FIG. 3A according to an embodiment. FIG. 3E shows a photographic image of the implementation of the scheme shown in FIG. 3B, where the fluorescent solution on the left contains a crosslinker, the fluorescent solution on the right contains a polymer and a reaction buffer, and the center stream contains an inert solution to prevent mixing of the left and right solutions before droplet splitting. The bright fluorescence between the center and right streams indicates a pH change in the center stream due to diffusion of the reaction buffer. FIG. 3F shows a photograph of the implementation of the scheme shown in FIG. 3B and FIG. 3E, while also showing an optical microscopic overview of droplet splitting after the constricting oil stream is introduced. [Figure 4] Figure 4A shows a top view of a microfluidic device according to another embodiment used to create multiple microgel particles as part of a microporous gel system. Figure 4B shows the constriction and division of the PEG pregel in the droplet division region by mineral oil containing 0.25% Span® 80, and the downstream 5% Span® 80 solution in mineral oil to prevent mixing and downstream microgel coalescence before full gelation. Figure 4C shows that the droplets do not recombine during incubation in the branching region and exit the microchannel into the collection well. [Diagram 5] FIG. 5 illustrates an exemplary microfluidic T-junction that can be used to generate microgel droplets, according to one embodiment. [Figure 6] Figure 6A illustrates an exemplary dispensing device in the form of a dual syringe according to one embodiment, Figure 6B illustrates an exemplary dispensing device in the form of a single syringe according to another embodiment, and Figure 6C illustrates an exemplary dispensing device in the form of a tube holding microgel particles according to one embodiment. [Figure 7]FIG. 7A shows hematoxylin and eosin staining (H&E staining) of tissue sections in SKH1-Hrhr mice for tissue injected with scaffold (Microporous Annealed Particle or "MAP" scaffold) and non-porous control 24 hours after injection. FIG. 7B shows a graph of wound closure (%) as a function of days after injection. The graph shows that there is a statistically significant improvement in wound closure rate over 5 days with scaffold use when compared to non-porous bilateral control (N=5). FIG. 7C shows representative images of wound closure in a 5-day in vivo wound healing model in SKH1-Hrhr mice comparing gel scaffold (left panel) to non-porous PEG gel control (right panel). FIG. 7D shows representative images of wound closure in a 7-day in vivo BALB / c experiment. After 7 days in vivo, the scaffolds promote significantly faster wound healing than untreated controls, gels lacking K and Q peptides, non-porous PEG gels, and preformed porous gels. Porous gels made ex vivo to precisely conform to wound shape using standard porogen-based molding methods showed comparable wound healing rates to the scaffolds, but lacked injectability (N>5). Figure 7E is a bar graph showing quantification data of wound closure from BALB / c in vivo wound healing, with each treatment group corresponding to Figure 7D. All data are expressed as mean + / - SEM. Statistical significance performed using a standard two-tailed t-test (*: p<0.05; **p<0.01). Figure 7F shows the in vivo follow-up of wound bed closure over 7 days, with each treatment group corresponding to Figure 7D and Figure 7E. FIG. 7G shows how a solution or slurry containing microgel particles is injected into the treatment site using an injection device such as the syringe of FIG. 6A or FIG. 6B (e.g., a 25 gauge syringe), where the microgel can conform to the shape of the injection site (e.g., in this case, an acrylic casting laser cut into a star shape) and then annealing the scaffold into the star shape. [Figure 8] FIG. 8A shows stained microscopic images of microgel scaffold-treated (FIG. 8A) and untreated or "sham" (FIG. 8B) damaged tissue (i.e., wound site) in a mouse model 21 days after skin excision and gel application. The scar reduction enabled by the microgel scaffold is clearly seen in FIG. 8A. The squares indicate hair follicles and oil glands (sebaceous glands) in the remodeling tissue after gel application to the wound. The circles indicate residual microgel particles in the remodeling tissue. FIG. 8B shows stained microscopic images of microgel scaffold-treated (FIG. 8A) and untreated or "sham" (FIG. 8B) damaged tissue (i.e., wound site) in a mouse model 21 days after skin excision and gel application. The scar reduction enabled by the microgel scaffold is clearly seen in FIG. 8A. The squares indicate hair follicles and oil glands (sebaceous glands) in the remodeling tissue after gel application to the wound. Circles indicate residual microgel particles in the remodeling tissue. FIG. 8C shows a graph showing epithelial thickness for sham-treated and gel scaffold-treated tissues. FIG. 8D shows a graph showing the number of sebaceous glands for sham-treated and gel scaffold-treated tissues. FIG. 8E shows a graph showing the number of hair follicles for sham-treated and gel scaffold-treated tissues. FIG. 8F shows a graph showing scar width for sham-treated and gel scaffold-treated tissues. FIG. 8G shows a graph showing the number of milia cysts for sham-treated and gel scaffold-treated tissues. [Figure 9]FIG. 9A shows a graph of storage modulus as a function of time after mixing at different gelation kinetics (pH and temperature). pH 8.25, 25° C. is represented by the bottom line of the graph; pH 8.8, 25° C. is represented by the top line of the graph; pH 8.25, 37° C. is represented by the middle line of the graph. FIG. 9B shows that the use of different hydrogel weight percentages produces different stiffness materials on the X-axis. The graph shows the storage modulus (Pa) at different hydrogel weight percentages. FIG. 9C shows the different crosslinker stoichiometries used to produce different stiffness values ​​in the resulting gels on the X-axis. The graph shows the storage modulus (Pa) as a function of the r ratio of free crosslinker ends (-SH) to vinyl groups (-VS) on the PEG molecule. FIG. 9D shows a graph of the degradation rate (%) as a function of time for both the non-porous control (bottom line of the graph) and the porous gels described herein (top line of the graph). Figure 9E shows SEM images of scaffolds annealed with FXIIIa at 200 μm (top panel) or 100 μm (bottom panel). Figure 9F shows SEM images of microgel particles without FXIIIa at 200 μm (top panel) or 100 μm (bottom panel). Unannealed microgel particles are seen in Figure 9F. [Figure 10] Figure 10 shows a microgel fabricated using the above technique, where the surface of the microgel is enhanced with fluorescent bovine serum albumin (BSA) protein (at the periphery) through the use of phosphine-azide "click" chemistry. Additionally, nanoparticles (500 nm) are embedded within the microgel during microfluidic fabrication. [Figure 11] 11 shows an exemplary method for treating damaged tissue using the microporous gel system described herein: Microgel particles are applied (top panel), an applicator is optionally used (second panel), annealing of the microgel particles is initiated to form a scaffold (third panel), and improved wound healing is observed (bottom panel). [Figure 12]Figure 12A shows fluorescence images showing the formation of a 3D cell network during 6 days of culture in a porous gel scaffold in vitro, and a non-porous gel after 6 days. (350 Pa: identical bulk modulus to the porous gel scaffold, 600 Pa: microscale modulus fitted to the individual microgels). Figure 12B shows a graph showing that cell survival 24 hours after annealing is greater than 93% across three cell lines representing various human tissue types. HDF: human dermal fibroblasts, AhMSC: adipose-derived human mesenchymal stem cells, BMhMSC: bone marrow-derived human mesenchymal stem cells. [Figure 13] FIG. 13A shows an exemplary method for mixing live cells with preformed microgel particles prior to annealing. The microgel particles anneal to each other, trapping the live cells in the interconnected microporous network that results after annealing of the microgel. FIG. 13B is a photographic image showing that a microgel particle solution mixed with live cells can be molded into macroscopic shapes and can be injected to form complex shapes that are maintained after annealing. FIG. 13B shows an exemplary in vitro injection with a syringe. FIG. 13C is a photographic image showing that a microgel particle solution mixed with live cells can be molded into macroscopic shapes and can be injected to form complex shapes that are maintained after annealing. FIG. 13C shows an exemplary in vitro molding. FIG. 13D is a photographic image showing that a microgel particle solution mixed with live cells can be molded into macroscopic shapes and can be injected to form complex shapes that are maintained after annealing. Figure 13D shows an exemplary in vitro annealed scaffold, and Figure 13E shows that the microgel particles can be molded into macroscopic shapes and can be performed in the presence of live cells (indicated by the arrow pointing to a fluorescent HEK-293T cell). [Figure 14]FIG. 14A shows a graph illustrating that microgel particles of various sizes can be synthesized over a range of generation frequencies in an exemplary embodiment. FIG. 14B shows that in another exemplary embodiment, applying high inlet pressures to each solution inlet (oil inlets above 30 Psi) allows for increased generation frequencies. FIG. 14C shows a graph illustrating that precision fabrication of microgel building blocks allows for the fabrication of defined gel scaffolds. Different building block sizes allow for deterministic control over the characteristics of the resulting microporous network, shown herein as median pore size + / - standard deviation (SD). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0030] In describing the preferred embodiments, reference is made to the accompanying drawings which form a part hereof, and in which is shown by way of illustration specific embodiments in which the inventive subject matter described herein may be practiced. It is to be understood that other embodiments may be utilized and structural changes may be made without departing from the scope or spirit of the inventive subject matter described herein. Additionally, various aspects of the various embodiments may be utilized with other embodiments described herein without departing from the scope of the present invention.

[0031] In one embodiment of the inventive subject matter described herein, a solid microgel scaffold for biomedical applications such as wound healing is disclosed that is formed when a plurality of microgel particles are annealed to one another in an annealing reaction. The annealing reaction, in one embodiment of the inventive subject matter described herein, forms covalent bonds between adjacent microgel particles. For example, in the annealed state, the scaffold forms a three-dimensional structure that conforms to the application or delivery site. Due to the incomplete packing of the microgel particles, the annealed scaffold formed from these particles includes gaps formed within the scaffold, in which cells can migrate, attach, and proliferate. The formed scaffold structure becomes porous after annealing at the wound site or other delivery site (unlike the non-porous solid scaffolds provided by fibrin-based products). This porosity includes the gaps and nanoscale pores that can be created or formed within the particles themselves. The microporosity of the scaffold structure allows for high diffusivity of nutrients, cell growth factors, and cell differentiation factors, as well as cell migration, ingrowth, and infiltration. The microporosity of the scaffold enhances cell migration through the interstices while maintaining the integrity of the entire scaffold, thus promoting healing or improving the delivery of therapeutic drugs or medical products over traditional fibrin glues, hyperbranched polymers, or polymers with any degradable crosslinker. Furthermore, by not limiting the biomaterial to natural materials, for example, it is possible to have a larger and more diverse range of biological signals, improving degradation characteristics and physical properties (e.g., stiffness, internal diffusivity, etc.), or to incorporate therapeutic chemicals into the material (e.g., antibiotics, steroids, growth factors, etc. can be loaded onto the scaffold). Furthermore, the release or elution of drugs, compounds, or other substances to induce or control biological activity can be tailored in some embodiments through the modification of the desired biomaterial. The above signaling compounds or molecules can be exposed to the tissue during the healing process or after scaffold degradation. The signaling compounds or molecules can also be released or eluted into the affected area after initial placement of the scaffold at the delivery site.

[0032] One advantage of the subject matter of the invention described herein over methods such as STAR™ technology is that the formation of the scaffold occurs in vivo, allowing it to be tailored to completely fill the desired space and to bond (chemically or otherwise) to the surrounding tissue. Furthermore, the pre-delivery formation of the microgel particles allows for control of the mechanical tunability of the resulting post-formation scaffold to match the properties of the surrounding tissue. These capabilities result in better sealing and overall integration with the tissue. Better integration results in reduced chances of material failure and enhanced long-term regeneration. This also helps prevent contamination from the environment. Additionally, the microporosity of the annealed scaffold is advantageous in reducing immune foreign body responses to the scaffold.

[0033] FIG. 1 illustrates a portion of a formed three-dimensional scaffold 10 formed by a plurality of annealed microgel particles 12. The scaffold 10 includes internal voids 14, which are voids that form micropores within the larger scaffold 10. The voids 14 have dimensions and geometric properties that allow cell infiltration, attachment, and proliferation. It will be appreciated that the microporosity of the scaffold 10 disclosed herein involves a network of voids or gaps 14 located between the annealed microgel particles 12 that form the larger scaffold structure. In one embodiment, the voids or gaps 14 created within the scaffold 10 exhibit negative concavity (e.g., the internal void surface is convex). FIG. 1 illustrates an exemplary void 14 with void walls 16 that exhibit negative concavity. The negative concavity results from the fact that, in one preferred embodiment, the microgel particles 12 that are annealed to one another are generally or substantially spherical in shape. This allows for a packing of microgel particles 12 resulting in a low void volume fraction, according to one embodiment from about 10% to about 50%, and in another embodiment from about 26% to about 36%. While the void volume fraction is low, the negative concavity shown in the embodiment within the network of voids 14 provides a relatively high surface area to the void volume for cells to interact with. For a given cell volume, cells will generally be exposed to more and larger surfaces (e.g., void walls 16) to interact within the void network within scaffold 10.

[0034] It is important to note that the void network consists of regions where the microgel surface is in close proximity (e.g., closely adjacent annealed microgel particles 12), providing high surface area attachment regions for cells to attach and rapidly migrate through, while the adjacent regions in the interstices between the microgel particles 12 have larger spaces that may allow cell proliferation and tissue growth within the spaces. Thus, the combined contiguity of close void regions and more open void gaps is expected to have a beneficial effect on tissue ingrowth and regrowth compared to overall small voids or all larger voids.

[0035] It should be noted that in the above embodiment, the negative concavity is caused by the spherical shape of the microgel particles 12. In other embodiments, the microgel particles 12 may not be spherical. Other non-spherical shapes may be used in the scaffold 10. Referring to FIG. 1, the scaffold 10 is formed by the microgel particles 12 locking together via an annealing surface 17. As described herein, the annealing surface 17 is formed during or after application of the microgel particles 12 to a desired delivery site.

[0036] The scaffold 10 may be used in a variety of applications, including a variety of medical applications such as warfare medicine, medical trauma care, post-operative closure, burns, inflammatory, genetic, and autoimmune blistering diseases, etc. In one or more embodiments, the scaffold 10 is used as a tissue sealant (e.g., acute wound healing material, surgical sealant, topical agent for partial thickness, full thickness, or tunnel wounds, decubitus ulcers, venous ulcers, diabetic ulcers, chronic vascular ulcers, donor skin graft sites, post-Mohs surgery, post-laser surgery, podiatric wounds, wound dehiscences, abrasions, lacerations, second or third degree burns, radiation injuries, skin lacerations, and draining wounds, etc.). Figures 2A-2C illustrate an embodiment in which the scaffold 10 is used to treat a wound site 100 formed in mammalian tissue 102. In one embodiment, the scaffold 10 is used for the emergency treatment of acute wounds. In acute wounds, the scaffold 10 offers several advantages, including a rapid method for sealing the wound 100, preventing transepidermal water loss, delivering cells or drugs, and enhancing the healing of skin wounds (e.g., surgical sites, burns, ulcers) to provide more natural tissue development (e.g., avoiding the formation of scar tissue). One particular advantage of the scaffold 10 is the ability of the scaffold 10 to reduce or minimize the formation of scar tissue. The scaffold 10 offers a more effective alternative to tissue glues and other current injectable tissue fillers and injectable tissue adhesives.

[0037] As shown in FIG. 2A, after the microgel particles 12 are delivered to the wound site 100, an annealing reaction is initiated and the microgel particles 12 anneal to each other to form the scaffold 10. As shown in FIG. 2A, the wound site 100 is sealed by the scaffold 10, and over time, the wound site 100 heals to normal tissue (see also FIG. 11). FIG. 2B illustrates how adjacent microgel particles 12 (particle A and particle B) chemically or enzymatically initiate an annealing reaction to form an annealed surface 17 between the microgel particles 12. FIG. 2C shows a close-up view of how the porosity of the scaffold 10 allows the scaffold 10 to act as a structural support while allowing tissue infiltration and biomaterial absorption. Cells 106 are shown infiltrating into the gaps formed within the scaffold 10.

[0038] The scaffold 10 may also be utilized in a regenerative capacity, for example, applied to tissues for burns, acute and chronic wounds, etc. In one embodiment, the scaffold 10 is used for chronic wounds. In chronic wounds where normal healing processes are inhibited, the scaffold 10 can be used to not only seal the wound, but also remove excess water and apply medicinal agents, including, for example, cell therapy, which may help promote normal wound healing processes. For tissue filler applications for volume loss associated with aging, lipoatrophy, lipodystrophy, skin scarring, or superficial or deep wrinkles, direct injection of the microgel particles 12 into the dermis via a needle or cannula may be used to improve tissue contour, tissue defect, or tissue displacement. Since cells used in regenerative medicine can grow within the microgel particles 12, cells (e.g., mesenchymal stem cells, fibroblasts, etc.) may be included as a therapy by first polymerizing the cells (1-20 cells) within the microgel particles prior to in situ annealing in the tissue, or the cells may be first adhered to the microgel particles, or the cells may be introduced with the microgel particle solution (non-adherent).

[0039] The scaffold 10 may also be used for in vitro tissue growth, three-dimensional (3D) matrices for bioscience research, as well as cosmetic and dermatological applications. For example, cancer cells may be seeded with the microgel precursor and, after annealing, may allow for rapid 3D growth of tumor spheroids for more physiologically relevant drug testing without the need for matrix degradation that would be required with other 3D culture gels (e.g., Matrigel®). The ability to rapidly form cell-cell contacts within the 3D matrix of the annealed gel is expected to enhance the growth and formation of microtissues from a single cell type or multiple cell types, which may be used for drug screening or cosmetic testing. An epidermal layer may be formed on the surface of the scaffold 10, which may allow for the testing of drugs or cosmetics on a more skin-like alternative compared to animal models. Previous 3D culture materials may allow cell seeding within the gel uniform throughout the volume, but may be unable to maintain cell-cell contacts due to lack of porosity, or may create porosity but require cell seeding and cell migration into the scaffold after assembly.

[0040] As described herein, the annealed scaffold 10 typically forms a defined structure, while the precursor material prior to final annealing is flowable and can be delivered as a paste, slurry, or even injected to the intended delivery site. While other injectable hydrogels can provide a scaffold for in situ tissue regrowth and regeneration, these injectable materials require gel degradation prior to tissue remodeling, which limits their ability to provide physical support. The injectable microporous gel system described herein circumvents this problem by providing an interconnected microporous network for simultaneous tissue remodeling and material degradation.

[0041] Microfluidic formation allows substantially monodisperse microgel particles 12 to form interconnected microporous annealed particle scaffolds 10 (in one embodiment of the inventive subject matter described herein), thereby allowing control of the chemical, physical, and geometric properties of the microgel particles 12 (e.g., building blocks), resulting in downstream control of the physical and chemical properties of the constructed scaffolds 10. In vitro, cells incorporated during scaffold 10 formation proliferate and form extensive three-dimensional networks within 48 hours. In vivo, the injectable gel system that forms scaffolds 10 promotes cell migration, resulting in rapid skin tissue regeneration and tissue structure formation within 5 days. The combination of microporosity and injectability achieved by scaffolds 10 enables novel pathways for tissue regeneration and new tissue formation in vivo.

[0042] FIG. 2A shows a scaffold 10 formed within a wound site 100. Successful tissue regeneration materials benefit from precisely matching the material degradation rate to tissue development. If degradation occurs too quickly, insufficient scaffold remains to support tissue ingrowth. Conversely, a rate that is too slow can prevent proper tissue development and encourage fibrosis and / or immune rejection. Tuning the degradation rate based on the local environment has been addressed using hydrolytically and enzymatically degradable materials. However, decoupling loss of mechanical stability of the material with cell infiltration has proven to be very troublesome. Facilitating cell infiltration into the material can also be addressed using lightly crosslinked matrices, but this often results in mechanical mismatch with the surrounding tissue and lack of material stability. Alternatively, hydrogel degradation rate can be tuned by altering the polymeric backbone identity or crosslink density to match the degradation rate with tissue formation. Although these techniques can be tailored to address specific applications of injectable hydrogels, they do not provide a robust route to achieve bulk tissue integration without relying on reduced material stability.

[0043] Every wound site is unique in its physical, chemical, and degradation requirements for functional tissue regeneration, requiring a material strategy that is agnostic to a variety of hostile environments. The microporous gel system and resulting scaffold 10 fabricated as described herein avoids the requirement for material degradation prior to tissue ingrowth by providing a stably connected and interconnected micropore network for cell migration and bulk integration with surrounding tissue. The microporous gel system achieves these favorable characteristics by utilizing the self-assembly of microgel particles 12 as "building blocks" or "subunits" formed by microfluidic water-in-oil droplet partitioning, according to one embodiment. According to one embodiment, the microgel particles 12 thus formed are substantially monodisperse. The microgel particles 12 can be injected and molded into any desired shape. The lattice of microgel particles 12 then anneals to each other via surface functional groups to form an interconnected microporous scaffold 10 with or without cells present within the interconnected porous network. In one embodiment, the scaffold 10 preferably comprises covalently linked microgel particles 12 that form a three-dimensional scaffold 10 for tissue regeneration and ingrowth.

[0044] By combining injectability with microporosity, the microporous gel system provides an ideal biomaterial scaffold for efficient cell network formation in vitro and bulk tissue integration in vivo. The modular microporous gel system also provides molecular cues for rapid cell migration, direct cell adhesion, and mechanical support for resorption during and after tissue regeneration. Through microfluidic fabrication, the chemical, physical, and geometric properties of the microgel particles 12 can be predictably and uniformly tuned, allowing downstream control of the properties of the temporary scaffold 10. The novel building block-based approach, where robustly achieved incomplete self-assembly is desirable to achieve microporosity, fundamentally changes the use and implementation of hydrogels as tissue-mimetic constructs and represents a mindset change in the approach to injectable scaffolds for bulk tissue integration.

[0045] In one aspect of the subject matter described herein, the microporous gel system employs microgel particles 12 having diameter dimensions in the range of about 5 μm to about 1,000 μm. The microgel particles 12 can be made from hydrophilic polymers, amphiphilic polymers, synthetic or natural polymers (e.g., poly(ethylene glycol) (PEG), poly(propylene glycol), poly(hydroxyethyl methacrylate), hyaluronic acid (HA), gelatin, fibrin, chitosan, heparin, heparan, and synthetic forms of HA, gelatin, fibrin, chitosan, heparin, or heparan). In one embodiment, the microgel particles 12 are made from any natural polymer (e.g., modified HA) or synthetic polymer (e.g., PEG) capable of forming a hydrogel. In one or more embodiments, polymer networks and / or any other support network capable of forming a solid hydrogel construct can be used. Support materials suitable for most tissue engineering / regenerative medicine applications are generally biocompatible and preferably biodegradable. Examples of suitable biocompatible and biodegradable supports include natural polymeric carbohydrates and their synthetically modified, cross-linked or substituted derivatives, such as gelatin, agar, agarose, cross-linked alginate, chitin, substituted and cross-linked guar gum, cellulose esters, especially with nitrous acid and carboxylic acids, mixed cellulose esters and cellulose ethers; nitrogen-containing natural polymers such as proteins and derivatives, including cross-linked or modified gelatin, and keratin; vinyl polymers, such as poly(ethylene glycol) acrylate / methacrylate / vinylsulfone / maleimide / norbornene / allyl, polyacrylamide, polymethacrylic acid, copolymers and terpolymers of the above polycondensates, such as polyesters, polyamides and other polymers, such as polyurethanes; and mixtures or copolymers of the above classes, such as graft copolymers obtained by initiating the polymerization of a synthetic polymer onto an existing natural polymer.A variety of biocompatible and biodegradable polymers are available for therapeutic applications; examples include polycaprolactone, polyglycolic acid, polylactic acid, polylactic-co-glycolic acid (PLGA), and poly-3-hydroxybutyrate. Methods for fabricating networks from such materials are well known.

[0046] In one or more embodiments, the microgel particles 12 further include covalently attached chemicals or molecules that function as signaling modifications formed during the formation of the microgel particles 12. Signaling modifications include, for example, the addition of adhesive peptides, extracellular matrix (ECM) proteins, and the like. Functional groups and / or linkers can also be added to the microgel particles 12 after their formation through covalent methods or non-covalent interactions (e.g., electrostatic charge-charge interactions or diffusion limited sequestration). The crosslinker is selected depending on the desired degradation characteristics. For example, the crosslinker of the microgel particles 12 can be degraded by hydrolysis, enzymatically, photolysis, and the like. In one particular preferred embodiment, the crosslinker is a matrix metalloprotease (MMP)-degradable crosslinker.

[0047] Examples of these crosslinkers are sequences corresponding to MMP-1 target substrates, MMP-2 target substrates, MMP-9 target substrates, random sequences, Omi target sequences, heat shock protein target sequences, and synthetically produced or naturally isolated peptides having any of these listed sequences in which all or some of the amino acids are of D- or L-chirality. In another embodiment, the crosslinker sequences are hydrolytically degradable natural and synthetic polymers composed of the same backbones as above (e.g., heparin, alginate, poly(ethylene glycol), polyacrylamide, polymethacrylic acid, copolymers and terpolymers of the above polycondensates, e.g., polyesters, polyamides, and other polymers, e.g., polyurethanes).

[0048] In another embodiment, the crosslinker is a synthetically produced or naturally isolated DNA oligo with a sequence corresponding to a restriction enzyme recognition sequence, a CpG motif, a Zn finger motif, a CRISPR sequence or a Cas-9 sequence, a Talon recognition sequence, and a transcription factor binding domain.Any of the crosslinkers from the above embodiment are activated at each end with a reactive group, which is defined as a chemical group that allows the crosslinker to participate in a crosslinking reaction to form a polymer network or gel, and these functional groups can include cysteine ​​amino acid, synthetic and naturally occurring thiol-containing molecules, carbene-containing groups, activated esters, acrylates, norborenes, primary amines, hydrazides, phosphenes, azides, epoxy-containing groups, SANPAH-containing groups, and diazirine-containing groups.

[0049] In one embodiment, the chemistry used to create the microgel particles 12 allows for subsequent annealing and scaffold 10 formation via radically-initiated polymerization. This includes chemical initiators such as ammonium persulfate in combination with tetramethylethylenediamine. Alternatively, photoinitators such as Irgacure® 2959 or Eosin Y may be used in combination with a light source used to initiate the reactions described herein, along with a free radical transfer agent such as a free thiol group (used at concentrations in the range of 10 μM to 1 mM). One example of a free thiol group may include, for example, the amino acid cysteine ​​described herein. Of course, peptides containing free cysteine ​​or small molecules containing free thiols may also be used. Another example of a free radical transfer agent includes N-vinylpyrrolidone (NVP).

[0050] Alternatively, Michael and pseudo-Michael addition reactions involving α,β-unsaturated carbonyl groups (e.g., acrylates, vinylsulfones, maleimides, etc.) to nucleophilic groups (e.g., thiols, amines, aminoxy) may be used to anneal the microgel particles 12 to form the scaffold 10. In another embodiment, the chemistry of the microgel particle 12 formation allows for network formation via initiating a sol-gel transition, including that of fibrinogen to fibrin (via the addition of the catalytic enzyme thrombin).

[0051] Functional groups that allow for interparticle annealing are included during or after formation of the microgel particles 12. In one or more embodiments, these functional groups include α,β-unsaturated carbonyl groups that can be activated for annealing via either radical initiated reactions with α,β-unsaturated carbonyl groups on adjacent particles, or Michael and pseudo-Michael addition reactions with nucleophilic functional groups present exogenously as interparticle multifunctional linkers or as functional groups present on adjacent particles. The method may use multiple microgel particle 12 assembly types that form the scaffold 10 when mixed. For example, X-type microgel particles 12, for example, presenting nucleophilic surface groups, may be used with Y-type microgel particles 12, for example, presenting α,β-unsaturated carbonyl groups. In another embodiment, functional groups that participate in click chemistry may be included that allow for binding to adjacent microgel particles 12 presenting complimentary click functional groups, either directly or via exogenously presented multifunctional molecules (e.g., copper) that participate in or initiate the click reaction.

[0052] The annealing functionality may include any of the aforementioned functional groups used in microgel crosslinking that are orthogonal or similar (if latent reactive groups remain) in terms of their initiation conditions (e.g., temperature, light, pH) compared to the initial crosslinking reaction. For example, if the initial crosslinking reaction consists of a temperature-dependent Michael addition reaction, the subsequent annealing functionality may be initiated through temperature initiation or photoinitiation (e.g., Eosin Y, Irgacure®). As another example, the initial microgel may be photopolymerized at one light wavelength (e.g., ultraviolet wavelengths with Irgacure®) and annealing of the microgel particles 12 may occur at the same or another light wavelength (e.g., visible wavelengths with Eosin Y), or vice versa. In addition to annealing by covalent reactions, the annealing moieties may include non-covalent hydrophobic guest / host interactions (e.g., cyclodextrins), hybridization between complementary nucleic acid sequences or nucleic acid mimics (e.g., protein-nucleic acids) on adjacent microgel particles 12, or ionic interactions. An example of an ionic interaction would consist of alginate functional groups on the microgel particle surface being annealed with Ca2+. Microgel particles 12 can be annealed similarly by using so-called "A+B" reactions. In this embodiment, two separate microgel types (types A and B) are mixed in various ratios (0.01:1 to 1:100 A:B) and the surface functional groups of type A react with type B (and vice versa) to initiate annealing. These reaction types may be classified into any of the mechanisms described herein.

[0053] In one embodiment, the microgel particles 12 are fabricated using microfluidic or millifluidic methods that produce deterministic microgel particle length scales with small variations and at high throughput (e.g., frequencies greater than 10 particles / second). The coefficient of variation of the microgel particle 12 length scale (e.g., diameter) can be within 35% of the average length scale, or more preferably within 15%, and even more preferably within 5%. Millifluidics or microfluidics allows uniform, predefined, and concise material properties to be included before, during, and after the formation of the microgel particles 12. Furthermore, microfluidic / millifluidic fabrication mechanisms allow for ease of scale-up of production as well as good quality control over the chemical composition and physical characteristics of the microgel particles 12. Millifluidic and / or microfluidic techniques for microgel particle 12 production are processes that are easily scalable to produce large quantities of material for commercial demand while maintaining high accuracy and precision in the microgel particle 12 characteristics. Moreover, all of this is accomplished at a low cost compared to other techniques, including electrospinning or large-scale fibrin purification.

[0054] In one embodiment, the microgel particles 12 are formed using automated fluidic methods that rely on water-in-oil emulsion generation, including microfluidic or millifluidic methods that utilize glass / PDMS, PDMS / PDMS, glass / glass, or molded / cast / embossed plastic chips to create water-in-oil droplets with less than 35% size distribution variation.

[0055] 3A-3F show one embodiment of a microfluidic device 20 used to generate microgel particles 12. The microfluidic device 20 is formed in a base material 22, such as PDMS, which may include another base material 24 (e.g., glass) bonded to a substrate 22. In this embodiment, the microfluidic device 20 includes a first inlet 26, a second inlet 28, and a third inlet 30. As shown in FIG. 3A, the third inlet 30 is interposed between the first inlet 26 and the second inlet 28. In this embodiment, the first inlet 26 is coupled to a solution containing a four-arm poly(ethylene glycol) vinyl sulfone (PEG-VS) backbone (20 kDa) that has been pre-modified with an oligopeptide (e.g., RGD) for cell adhesion properties and surface / tissue annealing functional groups (e.g., K-peptide and Q-peptide). The PEG-VS backbone may be pre-functionalized with 500 μM K-peptide (Ac-FKGGERCG-NH2 [SEQ ID NO: 1]) (Genscript), 500 μM Q-peptide (Ac-NQEQVSPLGGERCG-NH2 [SEQ ID NO: 2]), and 1 mM RGD (Ac-RGDSPGERCG-NH2 [SEQ ID NO: 3]) (Genscript). The solution injected into the first inlet 26 may contain about 5% (by weight) modified PEG-VS contained in a 0.3 M triethanolamine (Sigma) buffer, pH 8.25. The second inlet 28 is connected to a solution containing a crosslinker, which in one embodiment is 12 mM di-cysteine ​​modified matrix metalloprotease (MMP) (Ac-GCRDGPQGIWGQDRCG-NH2 [SEQ ID NO: 4]) substrate (Genscript). In experiments performed using fluorescent imaging, the MMP substrate was pre-reacted with 10 μM Alexa-fluor647-maleimide (Life Technologies). Needless to say, in practical applications, the use of fluorescent probes is not necessary. All solutions can be sterile filtered through a 0.2 μm polyethersulfone (PES) membrane in a Luer-lock syringe filter.

[0056] As used herein, K-peptide refers to a peptide that contains the lysine group that is recognized by activated factor XIIIa.As used herein, Q-peptide refers to a peptide that contains the glutamine group that is recognized by activated factor XIIIa.Therefore, peptide sequences other than the peptide sequences specifically described above can also be used.The same applies to the RGD peptide sequence described above.

[0057] The third inlet 30 is connected to an aqueous solution containing 5 wt. % PEG-VS (not modified with K, Q, or RGD peptides). The PEG-VS aqueous solution is preferably viscosity matched to the PEG-VS solution introduced through the first inlet 26 and can be used to adjust the pH of the crosslinker solution and inhibit crosslinking until droplet formation. With the third inlet 30 inserted between the first inlet 26 and the second inlet 28, the PEG-VS aqueous solution acts as a barrier to prevent any mass diffusion mixing of the reactive solutions upstream of the droplet generation region. This significantly extends the lifetime of the device before fouling occurs. Figures 3E and 3F show how the inert solution prevents mixing of the left and right solutions before droplet division. It should be noted that the method of making microgel particles 12 also works by removing the third inlet 30 and adjusting the peptide / crosslinker concentrations accordingly, but the lifetime of the device is not significantly increased.

[0058] 3A, 3B, and 3C, the first inlet 26, the second inlet 28, and the third inlet 30 are connected to channels 32, 34, and 36, respectively. The channels intersect at a junction 38 and are contained within a common channel 40. A fourth inlet 42 is provided in the device and is connected to an oil phase containing a surfactant (e.g., 1% by volume SPAN® 80, although other surfactants can be used). The fourth inlet 42 is connected to two channels 44, 46 that intersect at a junction 48 in the downstream region of the common channel 40. The junction 48 in the device 20 is where aqueous droplets containing the PEG-VS component and the crosslinker are formed. The contents of the droplets undergo mixing and form microgel particles 12 after gelation, which in this embodiment is a function of ambient temperature and elapsed time. The device is provided with a fifth inlet 50 that is connected to another oil phase containing a higher volume percentage of surfactant than the oil phase connected to the fourth inlet 42. For example, the fifth inlet 50 may be connected to an oil phase containing 5% by volume SPAN® 80. Again, other surfactants besides SPAN® 80 may be used. The fifth inlet 50 is connected to two channels 52, 54 that intersect at a junction 56 in a constricting orientation as shown.

[0059] The common channel 40 continues into a series of increasingly divergent branch channels 58. The branch channels 58 allow for a continuous flow of the microgel particles 12 through individual parallel channels where the local environmental conditions can be adjusted as desired. For example, by adjusting the temperature of the individual branch channels 58, it is possible to control the crosslinking conditions of the microgel particles 12. Similarly, the light-activated reactions can be adjusted by irradiating the branch channels 58 with light. The microgel particles 12 can be removed from the device 20 using the outlet 59. However, it should be understood that the use of temperature control or light activation of the branch channels 58 is entirely optional, since the crosslinking reactions can also occur over time alone if the device is operated at or about ambient temperature.

[0060] As best shown in FIG. 3D, the first inlet 26, the second inlet 28, the third inlet 30, the fourth inlet 42, and the fifth inlet 50 are connected to flow lines 26', 28', 30', 42', and 50', respectively, which are connected to a pump device 51 or multiple pump devices 51 that pump the respective liquids to the similarly connected inlets 28, 28, 30, 42, 50. The pump device 51 may include separate pumps, each connected to a different liquid. Examples of pump types that may be used include syringe pumps or other pumps commonly used in connection with microfluidic devices. In one embodiment, the pump device 51 uses a controlled pressurized gas at the top of a reservoir to pump the liquid through the device at a desired flow rate.

[0061] 4A-4C show another embodiment of a microfluidic device 60 used to generate microgel particles 12. In this alternative embodiment, unlike the embodiment of FIGS. 3A-3C, there is no third inlet 30 carrying the aqueous solution used to separate the PEG and cross-linking moieties prior to droplet generation. Suitably, in this embodiment, the microfluidic device 60 comprises a first inlet 62, a second inlet 64, a third inlet 66, and a fourth inlet 68. The first inlet 62 is connected to a source of modified PEG-VS, for example as described above. The second inlet 64 is connected to a cross-linking agent. The third inlet 66 is connected to a source containing oil and surfactant. The fourth inlet 68 is connected to a source containing oil and surfactant in higher concentrations than the source connected to the third inlet 66. In this embodiment, the first inlet 62 and the second inlet 64 are each connected to channels 70, 72 that lead to a common channel 74. The third inlet 66 is connected to a channel pair 76, 78 that intersects with the common channel 74 at a junction 80 (best shown in FIG. 4B) where droplet generation occurs (the droplets form microgel particles 12 after reaction). The fourth inlet 68 is connected to a channel pair 82, 84 that intersects with the common channel 74 at a downstream location 86 relative to the junction 80 (best shown in FIG. 4B). As shown in FIG. 4A, the device 60 includes a series of gradually diverging branching channels 88 similar to those described in connection with the embodiment of FIGS. 3A-3C. The microgel particles 12 that pass through the branching channels 88 can be collected in a collection chamber 90 or the like that can be removed from the device 60. Liquid is delivered to the device 60 using the flow lines and pumping devices previously described in connection with the embodiment of FIGS. 3A-3C.

[0062] The fluid conditions that lead to the formation of microgel particles 12 include, in one embodiment, on-chip mixing of PEG-based and crosslinker-based aqueous solutions, one part containing the base polymer and the other containing the crosslinker or initiator. Of course, in the embodiment of Figures 3A-3C, there is three-input mixing containing the components + the addition of an aqueous inert stream. These PEG and crosslinker solutions are mixed in a volume ratio of 1:1 or in another controllable ratio up to 1:100 (controlled by the relative flow rates into the device). By adjusting the ratio of the oil flow rate and the total water flow rate, a specific size of microgel particles 12 is determined, where these ratios can range from 4:1 (water:oil) to 1:10 (water:oil).

[0063] As explained above, in the embodiment of Figures 3A-3D, the chip device 20 is designed to combine three aqueous solutions to form the microgel particles 12, with the base polymer and crosslinker / initiator separated by a non-reactive solution upstream of the droplet generator to prevent reaction of the solutions in the upstream region of droplet generation and fouling of the chip over time. In this configuration, the portion of the non-reactive solution should be equal to or less than the base and crosslinker solutions, and 1-0.05 times the volume ratio of the other solutions. In this manner, this embodiment can improve the reliability and lifespan of the chip used for microgel generation. Furthermore, in this or the previous embodiment, the introduction of cells into any of the two or three introduced aqueous solutions may allow the encapsulation of these cells (one cell or clusters of 2-20 cells per particle) within the microgel particles 12, such that the encapsulated cells can produce factors for enhancing wound healing or cell ingrowth.

[0064] While FIGS. 3A-3D and 4A-4C show different embodiments of microfluidic devices 20, 60 that can be used to generate microgel particles 12, in another embodiment, the microfluidic flow path can include a “T-shaped” structure, for example as shown in FIG. 5. In this embodiment, the microfluidic device 92 includes a junction formed between a first channel 94 that carries an aqueous phase, while a second channel 96 contains an oil phase. A droplet 97 is formed and conveyed through an outlet channel 98 (which may be the same as the first or second channel 94, 96). Alternatively, a different droplet formation configuration can be used to generate the microgel particles 12. For example, a device can utilize a gradient of confinement with non-parallel top and bottom walls to generate the droplet 97, such as the device disclosed in Dangla et al., Droplet microfluidics driven by gradients of confinement, Proc Natl Acad Sci USA, 110(3):853-858 (2013), which is incorporated herein by reference.

[0065] In the microfluidic device, the channel surfaces should be modified to be non-wetting by the aqueous phase, which may include surface fluorination, i.e., converting the surface to be hydrophobic or fluorophilic by covalent silane-based treatment or another non-specific adsorption-based approach. Alternatively, a plastic polymer containing fluorophilic groups may comprise the chip material and be combined with the surface coating, or no surface coating is performed. Furthermore, the oil used in the preferred embodiment should be mineral oil (paraffin oil) supplemented with a non-ionic surfactant, vegetable oil supplemented with an ionic surfactant, or fluorinated oil supplemented with a fluorinated surfactant (or any combination of these two oil / surfactant systems). These microfluidic or millifluidic methods produce monodisperse (less than 35% coefficient of variation) populations of microgel particles 12 at rates of 10 Hz or faster, with collection achieved manually or with an automated fluid handling system. Sufficient surfactant is needed to stabilize the pre-gel droplets to prevent coalescence of the microgel particles 12 before completion of the crosslinking reaction, but high levels of surfactant also destabilize the droplet generation process. Thus, a preferred embodiment of a microfluidic system for the production of microgel particles 12 includes a low concentration of surfactant in the initial constricted oil stream (1% or less) that produces droplets, and then an oil+surfactant solution from a separate inlet is added that is mixed with the formed droplets and oil and contains higher levels of surfactant (up to 10-fold, or even 50-fold higher than the initial surfactant). This is shown, for example, in the embodiments of Figures 3A-3D and 4A-4C.

[0066] In another embodiment, the two oil constriction flows have the same surfactant concentration. In yet another embodiment, there is no second constriction oil flow, and there is only a flow-focusing oil flow to generate droplets. Furthermore, as explained above, in some other embodiments, there is no second constriction oil flow, and only a T-junction oil flow is used to generate droplets. Of course, the T-junction droplet junction may be combined with a second focusing oil inlet having the same or greater surfactant concentration, if desired.

[0067] After formation, the microgel particles 12 are extracted from the oil phase using centrifugation through the aqueous phase or filtration through a solid membrane filtration device. For example, filtration can be used to reduce the volume of free aqueous solution (free volume) that holds the microgel particles 12. In one embodiment, the free volume of water is less than about 35% of the total volume. In another embodiment, to generate a deliberate polydisperse population, microgel particle generation is performed on a millifluidic or microfluidic platform to generate a stock of relatively monodisperse microgel particles 12 that are then mixed in a desired ratio to obtain a defined distribution and ratio of microgel particle 12 sizes. By precisely adjusting the ratio of microgel particle 12 sizes, the pore structure or chemistry of the final annealed scaffold 10 can be adjusted with stoichiometric ratios of 1:1, 10:1, or over 100:1.

[0068] Alternatively, the generation of microgel particles 12 via the water-in-oil droplet system can be carried out using acoustic mixing or a rotating vortex. These latter methods produce a polydisperse collection of microgel particles 12 with sizes ranging from 100 nanometers to 500 micrometers. These particles can then be filtered using porous filters, microfluidic filtration, or other techniques known in the art to obtain a narrower size distribution of the microgel particles 12 (e.g., coefficient of variation less than 50%). As another alternative, component microgel particles 12 of various shapes can be made using stop flow lithography, continuous flow lithography, and other methods for generating shaped particles that rely on shaped flow (see Amini et al. WO 2013 / 049404, incorporated herein by reference) in combination with UV-initiated polymerization through a shape-defining mask. In this case, the microgel particles 12 are non-spherical with lengths and widths that can vary from 5 to 1000 micrometers. Shaped particles can also be made by generating spherical particles in a water-in-oil emulsion and then extruding the particles through a microfabricated constriction with a length scale smaller than the diameter of the particle. The spherical particles take on the shape of the constriction as they transition into a gel and retain that shape as they gel at the constriction by any of the crosslinker reactions described above. The gel retains its shape after exiting the microfabricated construction. Shaped particles can allow for further pore control, overall porosity, pore tortuosity, and improved adhesion in the final scaffold formed by annealing the microgel particles 12.

[0069] In one or more embodiments, the microgel particles 12 are provided with biologically active molecules (e.g., small molecule drugs, antibiotics, peptides, proteins, steroids, matrix polymers, growth factors, antigens, antibodies, etc.) that may or may not be covalently modified (e.g., inclusion in the spatial interior by diffusion). Inclusion of signaling molecules after formation of the microgel particles 12 can be achieved by passive diffusion, surface immobilization (permanent or temporary), and / or bulk immobilization (permanent or temporary).

[0070] In another embodiment, nanoparticles are included in the initial prepolymer solution and incorporated into the microgel particles 12 during initial polymerization or gelation. The nanoparticles may contain biologically active molecules for sustained or rapid release and delivery. In another embodiment, microgel particles 12 containing free primary amines (included as part of a lysine-containing oligopeptide) may be modified with NHS-azide. To this end, a set of microgel particles 12 may be added with NHS-phosphine modified proteins, resulting in surface coating of the microgel particles 12 with the modified proteins. Figure 10 shows an embodiment in which microgel particles 12 have nanoparticles embedded therein and surfaces modified with proteins using click chemistry.

[0071] After generation and optional modification, the microgel particles 12 (which may be a homogenous or heterogenous mixture) may be applied to a desired site (in vitro, in situ, in vivo). The desired site on a mammalian tissue 102 may include, for example, a wound site 100 or other damaged tissue site. The microgel particles 12 may be introduced alone in an isotonic saline solution or slurry (a volume fraction of 30-99% microgel particles 12 is preferred, with a volume fraction of 1-30% being less preferred). Alternatively, the microgel particles 12 may be introduced with cells, either as single cells or clumps, with a cell:particle ratio of 10:1 to generate a dense cellular network within the final annealed scaffold 10, or 1:100 or 1:1000 to generate a low-density seeded scaffold 10 containing cells that produce soluble factors useful for regeneration. In another embodiment, microgel particles 12 can be cultured with cells at low particle volume fraction (less than 10%) for a period of time in cell-permissive media to promote adhesion to individual microgel particles 12. These cell-adhered microgel particle 12 complexes can be introduced as active ingredients that will anneal to form a microporous cell-seeded scaffold 10, which may be beneficial in increasing the rate of repair activity. Desirable in vitro sites for introducing microgel particles 12 include well plates (e.g., 6-well, 96-well, 384-well) or microfluidic devices to form a 3D microporous culture environment for cells after annealing, allowing subsequent bioassays or high-throughput screening assays with more physiologically relevant 3D or multicellular conditions. For in vitro introduction, a microgel particle 12 solution can be pipetted or introduced by syringe injection into the wells, followed by the introduction of an annealing solution or photochemical annealing. Alternatively, the microgel particle 12 solution can be mixed with a delayed annealing solution (annealing occurs over 10-30 minutes) prior to delivery.In situ sites include external wound sites (e.g., cuts, blisters, sores, decubitus ulcers, venous ulcers, diabetic ulcers, chronic vascular ulcers, donor skin graft sites, post-Mohs surgery sites, post-laser surgery sites, podiatric wounds, wound dehiscences, abrasions, lacerations, second or third degree burns, radiation injuries, skin lacerations and draining wounds, etc.). Since the epidermis is an epithelial structure, the microgel particle solution may be used to heal other epithelial surfaces (i.e., urothelium (bladder and kidney), aerodigestive tract (lung, gastrointestinal) as well as dermal epithelium (i.e., gastric or duodenal ulcers; following penetrating trauma to the lung, bladder, or intestinal fistula, etc.). Additionally, the microgel particle solution can be applied via catheter or cannula to other tissues, such as nervous and cardiac tissues where tissue ingrowth may be beneficial in preventing scarring and promoting restorative healing following injuries such as spinal cord trauma, cerebral infarction / stroke, and myocardial infarction.

[0072] For in situ delivery, the microgel particle-containing solution may be stored separately from the annealing solution and mixed during delivery (in a manner similar to epoxy adhesives) to prevent premature initiation of the annealing reaction prior to entry into the wound site 100.

[0073] Alternatively, the two solutions may be stored in a syringe or squeeze tube applicator with two barrels of equal or unequal diameter, such that when the plunger of the syringe is pressed or the squeeze tube is squeezed, both the microgel particles 12 and the annealing solution can be delivered simultaneously with the correct stoichiometry. Figure 6A shows one such embodiment of a delivery device 110 including a first barrel 112, a second barrel 114, and a plunger 116 used to dispense a solution containing the microgel particles 12 from each barrel 112, 114. For example, the first barrel 112 contains the microgel particles 12 and thrombin at a concentration ranging from 0.1 to 5 U / ml, and the second barrel 114 contains the microgel particles 12 and FXIII at a concentration ranging from 0.1 to 1,000 U / ml. Within both barrels 112, 114 are microgel particles 12 containing K and Q peptides in a 1:1 volume fraction, with the concentrations of K and Q peptides ranging from 10 to 1,000 μM in the microgel particles 12. In this embodiment, after mixing, thrombin activates FXIII (forming FXIIIa), which participates in surface annealing and ligation of K and Q peptides on adjacent microgel particles 12.

[0074] Alternatively, the two barrels 112, 114 may contain two separate microgel particle 12 types with annealing moieties that require combination to initiate crosslinking. Another method of storage and delivery would be in a single barrel syringe 110 as shown in FIG. 6B or in a compressible tube for multi-use or disposable use as shown in FIG. 6C (e.g., similar to toothpaste or antibiotic ointment) where the microgel particle slurry can be extruded to a desired volume, spread over the wound site 100, and then annealed through exposure to light where the active agent for photochemistry is Eosin-Y at a concentration of 100 μM, although concentrations in the range of 10 μM to 1 mM are also effective. Eosin-Y is preferably accompanied by a radical transfer agent, which may be, for example, a chemical species with a free thiol group. One example of one such radical transfer agent is cysteine ​​or a cysteine-containing peptide as described herein (e.g., used at a concentration of 500 μM). Light should be delivered via broad spectrum white light (incandescent or LED), or green or blue LED light. A flashlight, wand, lamp, or ambient light may also be used to provide white light. Exposure should occur for between 0.1 seconds and 1000 seconds, with light intensity of 0.01 mW / cm at the annealing site. 2 ~100mW / cm 2 In another embodiment, photo-mediated annealing can be achieved using ultraviolet light (wavelength 300-450 nm) and the agent for photochemistry is IRGACURE® 2959 at a concentration of 0.01% w / v to 10% w / v. Exposure time should be 0.1 seconds to 100 seconds and light intensity should be in the range of 0.1 mW / cm at the annealing site. 2 ~100mW / cm 2In embodiments where photoinitiated annealing is used, the microgel precursor 12 would be stored in an opaque (opaque to the wavelength range that will cause annealing) syringe or squeeze tube 110 container prior to use. Desired in situ sites include internal cuts and tissue gaps (e.g., from surgical incisions or excisions), burns, radiation wounds and ulcers, or in situ sites in cosmetic surgery applications to fill tissue sites and promote tissue ingrowth and regeneration rather than the fibrogenic process common to injectables today.

[0075] Delivery using a dual or single barrel syringe is suitable for this application, as well as for photoactivation and annealing using a UV or white light source insertable into the surgical site. In both in situ and in vivo applications, the microgel particle slurry can be spread with a sterile applicator to just overlap the wound or to pile up within and around the wound site 100 (within the wound and 2mm to 1cm beyond the original wound area) to create an annealed scaffold that extends across the wound site 100 or tissue that is deficient in providing additional protection, moisture, and structure to support tissue regeneration.

[0076] The annealing process is initiated through application of a stimulus (e.g., radical initiator, enzyme, Michael addition, etc.) or through interaction with a stimulus already present at the application site of the microgel particles 12 that interacts with functional groups on the surface of the microgel particles 12, thereby forming a solid, continuous, highly porous scaffold 10 formed from the annealed (linked) microgel particles 12. When used in tissues, the annealing process allows adhesion of the scaffold 10 to the surrounding tissue, which may provide effective sealing, a device for localized drug application and / or cell delivery, a vascularized scaffold for in vivo detection, and a better route to tissue regeneration. The annealing process allows for in situ / on-demand gel formation (ideal for in vitro and in vivo applications), for example, delivery through a small incision to a minimally invasive surgical site, or delivery by needle or injection through a catheter or cannula. The scaffold 12 may be composed of a uniform or heterogeneous collection of microgel particles 12. As discussed, a heterogeneous population of microgel particles 12 may have variations in physical properties (e.g., variations in size, shape, or stiffness) or variations in chemical composition (e.g., variations in degradable linkers or ratios of L- or D-amino acids that alter degradation rates, variations in annealing moieties, cell adhesion moieties, or loading of bioactive molecules or nanoparticles on the microgels 12). The heterogeneous composition of the final annealed scaffold 10 may be disordered or constructed in layers of uniform composition, resulting in gradients in microporous structure (e.g., due to variations in microgel particle 12 size within a layer) or gradients in chemical composition (due to layers of microgel particles 12 with different compositions or bioactive molecule loading). Gradients may be useful in directing cell ingrowth and tissue regeneration in vivo or the development of tissue structures in vitro. A gradient in microgel particle 12 composition can be achieved by successively delivering and subsequently annealing a gel slurry of a single composition, then delivering and subsequently annealing the next gel of a second composition, linking each new microgel layer to the previous layer until the desired number of layers has been deposited.The thickness of each layer can be adjusted using the volume of the slurry injected and the area of ​​the injection site. Another embodiment for achieving a gradient is the loading of a multi-barrel syringe applicator, such as the applicator shown in FIG. 6A, with a different microgel composition in each barrel. Each barrel is simultaneously pressurized and fed into the nozzle 120 in a layered sheet. The nozzle 120 of the syringe applicator itself can be non-circular or rectangular to produce a multi-composition layered slurry that is injected into the site in a band-like structure, and the layered slurry can then be annealed in this configuration. The formation of a structurally continuous annealed scaffold 10 can be achieved through radical, enzymatic, or chemical (e.g., click chemistry) processes.

[0077] In one or more embodiments, annealing occurs through interfacial chemical interactions between the microgel particles 12 after the microgel particles 12 are ready to be placed at the delivery site. In one embodiment, the process occurs through radical-initiated annealing (e.g., radical initiation by a photosensitive radical initiator, etc.) via surface polymerizable groups. In another embodiment, the process occurs through enzymatic chemistry via an enzymatically activated substrate (e.g., a transglutaminase enzyme such as activated factor XIIIa) presented on the surface. In another embodiment, the process occurs through covalent bonding via Michael and pseudo-Michael addition reactions. The method may employ multiple types of microgel particle assemblies that form a solid scaffold 10 upon mixing (e.g., microgel particle type 12A, e.g., presenting nucleophilic surface groups, and microgel particle type 12B, e.g., presenting α,β-unsaturated carbonyl groups). In another embodiment, the process occurs through click chemistry bonding. Similarly, the method may employ heterogeneous microgel particle 12 assemblies that form a solid microporous gel upon mixing. In another embodiment, annealing can be accomplished using light (e.g., white or ultraviolet light) to initiate chemical reactions between molecules on the gel surface via dissolved photoactivatable molecules within and surrounding (or directly covalently attached to) the microgel as described herein.

[0078] In one preferred embodiment, the microgel particles 12 comprise a PEG-based polymer backbone in combination with an enzymatically degradable crosslinker to enable bioabsorption. In one embodiment, the PEG-based polymer backbone is a four-arm poly(ethylene glycol)vinylsulfone (PEG-VS) backbone pre-modified with oligopeptides (e.g., RGD) and surface annealing functional groups (e.g., K-peptides and Q-peptides) for cell adhesion properties, and the crosslinker is a matrix metalloprotease (MMP)-degradable crosslinker.

[0079] In one or more embodiments, the microgel particles 12 are formed by a water-in-oil emulsion. Gelation of the microgel particles 12 occurs after mixing of the PEG and crosslinker solutions (which then split into microgel droplets immediately before gelation is complete). Various substrates, including peptide ligands, may be added for enhanced bioactivity. In one embodiment, scaffold formation is achieved by inducing chemical crosslinking by addition and activation of a radical photoinitiator to the purified microgel particles 12. In another embodiment, scaffold formation is achieved by inducing enzymatic crosslinking by use and / or activation of the endogenously present or exogenously applied transglutaminase enzyme, factor XIII, to the purified microgel particles 12 modified with two peptide ligands before, during, or after formation. In another embodiment, scaffold formation is achieved using a combination of the aforementioned radical and enzymatic methods.

[0080] The resulting scaffold 10 of the subject invention of the present disclosure offers advantages over current porous scaffold technology due to its ability to form a fully interconnected microporous scaffold in vivo. In general, porous scaffolds provide better access to living cells due to the freedom of movement through the pores (i.e., they do not require degradation to allow penetration, as all current and previous non-porous and nanoporous scaffolds do). For example, upon implantation and annealing of scaffold 10 in a skin wound in vivo, significantly enhanced cell infiltration and growing tissue structure was observed after 5 days when compared to a non-porous gel of the same material, as shown in FIG. 7B. FIG. 7A shows the SKH1-Hr MAP scaffold-injected tissue for tissue injected with scaffold 10 (identified as a MAP scaffold) and a non-porous control 24 hours after injection. hr Figure 7B shows a graph of wound closure (%) as a function of days after injection. The graph shows that there is a statistically significant improvement in the rate of wound closure over a 5-day period using scaffold 10 when compared to the non-porous bi-lateral control (N=5). Figure 7C shows the results of the SKH1-Hr hr Representative images of wound closure in a 5-day in vivo wound healing model in mice are shown. FIG. 7D shows representative images of wound closure in a 7-day in vivo BALB / c mouse experiment. FIG. 7E shows quantification data of wound closure from BALB / c in vivo wound healing. After 7 days in vivo, scaffold 10 promotes significantly faster wound healing than untreated control, non-porous PEG gel, and gel lacking K and Q peptides. Porous gels made ex vivo to precisely conform to wound shape using standard porogen-based molding methods showed comparable wound healing rates to scaffold 10, but lacked injectability (N>5). FIG. 7F shows the in vivo tracking of wound bed closure over 7 days, with each treatment section corresponding to FIG. 7D.

[0081] Additionally, therapeutic agents applied to the microgel particles 12 or scaffold 10 can be released slowly or quickly, and the scaffold 10 has the ability to degrade over a given time by hydrolysis, proteolysis, or enzymatic degradation depending on the intended treatment (e.g., when used to treat chronic wounds, more stable crosslinkers that degrade slowly over a long period of time are used). Additionally, the annealing properties of the microgel scaffold 10 allow the scaffold 10 to function as a tissue sealant (e.g., acute wounds, surgical closure, etc.) and as a filler for various molded shapes that are clinically useful to mimic tissue. FIG. 7G shows how a solution or slurry containing microgel particles can be applied to a treatment site using an injection device such as the syringe of FIG. 6A or FIG. 6B, where the microgel can conform to the shape of the injection site (e.g., in this case, a star-shaped site), and the subsequent annealing of the scaffold 10 into a star shape.

[0082] By adjusting the degradation rate of the microgel scaffold 10, the scar formation or regeneration response in the wound can be altered. In one embodiment, the degradation rate of the microgel scaffold 10 was altered by using D-amino acids instead of L-amino acids in the MMP degradable crosslinker. By adjusting the ratio of the microgel particles 12 along with the D- or L-chirality in the crosslinker, the degradation rate in the tissue was adjusted. In vivo, scaffolds 10 made from a mixture of D and L crosslinked microgels (1:1 ratio) resulted in gel present in the tissue 21 days after injection, whereas D-only gels left no residual gel after 21 days. Tissue healing and scarring response also depend on the stoichiometry of D:L and therefore on the rate of degradation. Figures 8A-8G show the effect of scar reduction using a 1:1 mixture of D:L in direct comparison to an untreated wound. In a 1:1 D:L gel treatment, the skin thickness is doubled and the scar size is reduced by 25%. Additionally, there are six times more hair follicles and sweat glands in the gel-treated cases compared to the untreated cases. EXAMPLES

[0083] A microfluidic water-in-oil emulsion method was used to divide the continuous pre-gel aqueous phase into the uniform scaffold building blocks described herein. The generation of microgel particles 12 as building blocks continuously at a minute scale, without the use of typical vortexing and sonication-based methods, allowed for tight control over the formation environment and the final material properties of the resulting scaffold 10. By adjusting the flow rates of both the pre-gel solution and the constricted oil flow, as well as the geometry of the microfluidic channel, a range of microgel particle sizes was generated with low polydispersity. Although the fabrication method was continuous, it remained practical in its high-throughput nature, with generation rates ranging from 250 Hz for large particles (>100 μm) to ∼1200 Hz for small particles (∼15 μm). This translated to approximately 100 μl of swollen pre-gel per device every 50 min. This method ultimately yielded particles that were highly monodisperse, both physically and chemically. Microfluidic generation of microgel particle "building blocks" is a readily scalable process, a practical requirement for widespread adoption and use.

[0084] The resulting microgel particles 12 consisted of a fully synthetic hydrogel mesh of a poly(ethylene)glycol-vinylsulfone (PEG-VS) backbone decorated with a cell adhesive peptide (RGD [SEQ ID NO:3]) and two transglutaminase peptide substrates (K [SEQ ID NO:1] and Q [SEQ ID NO:2]). The microgel particles 12 were crosslinked by Michael addition of cysteine-terminated matrix metalloprotease-sensitive peptide sequences, allowing cell-controlled material degradation and subsequent resorption.

[0085] The microgel particles 12 were purified in an aqueous solution of isotonic cell culture medium for storage and, when used for gel formation, were annealed to each other via a non-standard amide bond between the K and Q peptides, mediated by activated factor XIIIa (FXIIIa), a naturally occurring enzyme involved in stabilizing blood clots. This enzyme-mediated annealing process allowed the incorporation of live cells into the dynamically forming scaffold 10 containing an interconnected microporous network. After addition of FXIIIa, but prior to scaffold annealing, a slurry of microgel particles 12 was delivered via syringe application and was eventually allowed to solidify in the shape of the injected cavity. Figure 9A shows how adjustments of pH and temperature can alter annealing kinetics. The annealing environment chosen for this experiment was pH 8.25, and a temperature of 37°C.

[0086] Structural changes resulting in a more than three-fold increase in the storage modulus of the annealed gel were observed following the addition of FXIIIa to microgel particles 12. Annealing was confirmed to be necessary for scaffold formation via high-vacuum SEM observations, where after dehydration the scaffolds adopted the shape of a highly stretched but interconnected network, whereas building blocks without FXIIIa separated into individual spherical beads (Figure 9E).

[0087] By tuning the microgel particle size and composition, a variety of construction scaffolds 10 could be generated. By using microgel particles 12 with diameters of 30-150 μm, networks with median pore sizes ranging from about 10 to about 35 μm were achieved. Sieving different PEG weight percentages and crosslinker stoichiometries demonstrated a range of readily achievable storage moduli from about 10 to 1000 Pa, spanning the stiffness regime required for mimicking mammalian soft tissue. Figure 9B shows that the use of different hydrogel weight percentages produces materials with different stiffness. Figure 9C shows the different crosslinker stoichiometries (r ratio of crosslinker ends (-SH):vinyl groups (-VS)) used to produce different stiffness values ​​in the resulting gel. Figure 9D shows a graph of the degradation rate (%) as a function of time for both the nonporous control and the porous gels of the invention described herein. The degradation kinetics of particle-based porous and nonporous gels for equal volumes of gel in vitro are shown. Particle-based porous gels degrade faster than non-porous gels due to the larger surface area to volume ratio and faster transport within the microporous gel. Degradation was performed with 1:1000 TrypLE®, resulting in higher protease concentrations and faster degradation kinetics than in the wound bed. Figure 9E shows an SEM image of a scaffold annealed with FXIIIa. Figure 9F shows an SEM image of microgel particles 12 without FXIIIa. Unannealed particles are seen in Figure 9F.

[0088] To evaluate the ability of the generated scaffolds to support cell growth and network formation, an in vitro cell morphology and proliferation model was developed using three human cell lines. These included dermal fibroblasts (HDF), adipose-derived mesenchymal stem cells (AhMSC), and bone marrow-derived mesenchymal stem cells (BMhMSC). Single cell suspensions were dynamically incorporated into the FXIIIa-annealed gels. The three cell lines showed high cell viability (>93%) after 24 hours of in-scaffold culture. HDF and AhMSC cell lines showed continuous proliferation over a 6-day culture period, with doubling times of 1.5 and 2 days, respectively. BMhMSC were also observed to undergo proliferation, but an extended doubling time of approximately 12 days was calculated.

[0089] Cells incorporated into the scaffolds began to show an expanded morphology 90 min after the initiation of annealing. After 2 days of culture, all observed cells in the scaffolds showed a fully expanded morphology, which persisted through day 6. Importantly, extensive network formation was observed by day 2 in all cell lines. The cellular networks increased in size and complexity throughout the experiment. BMhMSCs were particularly noteworthy because their expandable network formation and slower proliferation rate indicated that these cells were able to spread to extreme lengths and form highly interconnected cellular networks within the microporous scaffolds. Notably, cells grown in nonporous gels of identical chemical (5 wt%, G = 600 Pa gel) and mechanical properties (4.5 wt%, G = 350 Pa gel) maintained viability but did not show obvious network formation, even after 6 days of culture.

[0090] It was hypothesized that the ability of the scaffold to allow both cell proliferation and appropriate network formation in vitro would be indicative of its ability to support cell migration and bulk tissue integration within the scaffold in vivo. To test this hypothesis, a mouse skin wound healing model was used to probe the target tissue with pre-implanted porous biomaterials. Importantly, preventing wound contraction with rubber splint sutures that limit closure for tissue ingrowth better stimulated a human healing response. The injectability of the microgel particle-based scaffolds allowed the microgel particles to be delivered directly to the wound site and then annealed in situ via exogenous FXIIIa. This resulted in a seamless interface due to the microgel particle "building blocks" simultaneously linking to each other and to endogenous lysine and glutamine residues present in the surrounding tissue. A similar seamless interface was observed in a chemically identical, non-porous bi-lateral control. Although their interfaces are similar, the generated scaffolds are similar to the CLR:SKH1-Hr scaffolds, as shown in Figure 7B. hr When injected into mouse wounds, it resulted in significantly faster wound closure than the non-porous control (60% vs. 100% remaining wound area after 5 days, respectively).

[0091] The difference in wound closure rates led to the study of the differences in tissue response to non-porous and injectable partible-based gels. Scaffold injection with microgel particles resulted in extensive wound re-epithelialization after 5 days in vivo. Keratin-5 + Cells were observed over the apical surface of the scaffold with a stratified squamous epithelial morphology, whereas cells (keratin-5) were observed over the non-porous wound edge. + No keratin-5 endothelial cell death or other abnormalities were observed. Importantly, the scaffolds were able to support the formation of what appeared to be complete hair follicles with adjacent sebaceous glands within the wound bed, resembling the structure of the glands in unwounded skin. Furthermore, the scaffolds were able to support the formation of large keratin-5 endothelial cell death and other abnormalities, including tubular structures and epithelial invaginations. +Other examples of tissue structures were observed within the scaffolds. Taken together, these results are hypothesized to represent a higher order collective migration (i.e., the concerted movement of multicellular clusters) that contributes to epithelial regeneration. Although cells were able to invade non-porous bi-lateral controls (as shown by DAPI staining), no evidence of re-epithelialization or skin tissue formation was found after 5 days in vivo.

[0092] Through further studies, it was found that the scaffold promoted bulk integration through complex vascular network formation in vivo. After 5 days, both endothelial cells and supporting pericytes were present within the scaffold, whereas in the nonporous bilateral control, only a single branch of endothelial cells was present without supporting pericytes. The presence of coexisting endothelial cells and pericytes was evidence of mature vascular network formation. To our knowledge, this is the first example of early (<7 days) pericyte migration into a synthetic injectable material or implanted porous scaffold without exogenous growth factors.

[0093] While examining the seamless interface provided by the injectable scaffolds, we observed differences in both total cell content and immune cell content at day 1. One day after injection, the scaffolds contained a significantly higher number of cells within the scaffold compared to their non-porous bi-lateral controls. This confirmed the enhanced ease of cell migration previously observed in our in vitro network formation experiments. Furthermore, the scaffolds and the surrounding tissue contained significantly lower numbers of polymorphonuclear cells when compared to non-porous bi-lateral controls from the same mice. This result indicated an overall lower initial innate immune response to the scaffolds at day 1. Five days after injection, a lower fraction of CD11b cells was detected in the scaffolds compared to the non-porous controls. +Cells (activated leukocytes) were present in both the surrounding tissue and within the scaffold, indicating a sustained, lower level inflammatory immune response consistent with that observed in ex vivo constructed and implanted microporous scaffolds. Taken together, these two results support the current investigation into the geometric component to immune stimulation from chemically identical injectable biomaterials.

[0094] Annealed microgel particle-based scaffolds are a new class of injectable biomaterials that introduce microscale interconnected porosity through robust incomplete self-assembly and annealing of the individual building blocks. This method allows control of microscale and hierarchical macroscale properties through defined chemical composition and microfluidic particle generation. Both entrapped living cells and surrounding host tissues can instantly infiltrate the scaffold without the need for material degradation, a feat that has never been achieved with an injectable scaffold.

[0095] In vivo, the injectable microgel particles completely filled tissue voids, resulting in a seamless interface with the surrounding tissue. The interconnected microporosity of the resulting scaffolds promoted cell migration at the wound site resulting in greater bulk integration with the surrounding tissue while eliciting an attenuated host immune response when compared to injectable nonporous controls. Ultimately, this resulted in faster healthy tissue remodeling than with similarly constructed injectable nonporous gels.

[0096] This gel system represents a fundamental change in the bottom-up modular biomaterials approach by exploiting lattice-forming negative spaces to facilitate the development of complex three-dimensional networks on timescales not previously seen with current hydrogel technology. The "plug-and-play" nature of this strategy allows for the incorporation of a wide range of already established materials (e.g., fibrin), signals (e.g., growth factors), and cell populations (e.g., stem cells). Complex combinations of building blocks with defined chemical and physical properties may enable tissue regeneration in a series of different physiological niches (e.g., nerve, heart, skin, etc.), where particle-annealed scaffolds are tailored to each niche via their building block properties. The unique combination of microporosity, injectability, and modular assembly inherent to the scaffolds has the potential to transform the landscape of tissue regeneration and de novo tissue formation in vivo.

[0097] Microfluidic water-in-oil droplet generators were fabricated using soft lithography as previously described. Briefly, master molds were fabricated on mechanical grade silicon wafers (University wafers) using KMPR1025 or 1050 photoresist (Microchem). Various channel heights were obtained by spinning the photoresist at different speeds as suggested by the manufacturer. Devices were cast from the master molds using poly(dimethyl)siloxane (PDMS) SYLGARD® 184 kit (Dow Corning). Base and crosslinker were mixed in a 10:1 mass ratio, sprinkled onto the mold, degassed, and then cured at 65 °C for 6 h. The channels were sealed by treating the PDMS mold and glass microscope slide (VWR) with oxygen plasma at 500 mTorr and 75 W for 15 s. Immediately after sealing the channel, the channel was functionalized by injecting 100 μl of RAIN-X® solution and allowing it to react for 20 minutes at room temperature. The channel was then air-dried and then dried overnight.

[0098] Droplets were generated using the microfluidic water-in-oil partitioning system shown in Figures 3A-3F and 4A-4C. The aqueous phase is a 1:1 volumetric mixture of two parts: (i) 10% w / v 4-arm PEG-VS (20 kDa) in 300 mM triethanolamine (Sigma) (pH 8.25) pre-functionalized with 500 μM K-peptide (Ac-FKGGERCG-NH2 [SEQ ID NO:1]) (GenScript), 500 μM Q-peptide (Ac-NQEQVSPLGGERCG-NH2 [SEQ ID NO:2]), and 1 mM RGD (Ac-RGDSPGERCG-NH2 [SEQ ID NO:3]) (GenScript), and (ii) 8 mM (12 mM for 3-inlet device) di-cysteine-modified matrix metalloproteinase (MMP) (Ac-GCRDGPQGIWGQDRCG-NH2 [SEQ ID NO:4]) (GenScript) substrate pre-reacted with 10 μM Alexa-fluor647-maleimide (Life Technologies). All solutions were sterile filtered through a 0.2 μm polyethersulfone (PES) membrane in a Leur-Lok syringe filter prior to use in the splitting system.

[0099] The production was carried out at 37 °C on an incubator (NIKON® Eclipse Ti) for real-time tracking of microgel quality. The input aqueous solution was almost completely mixed (Peclet number >10) until droplet segmentation. The oil phase was heavy mineral oil (Fisher) supplemented with 0.25% v / v SPAN® 80 (Sigma-Aldrich). Downstream of the segmentation region, a higher concentration of SPAN® 80 (5% v / v) was added to a second oil inlet and allowed to mix with the flowing droplet emulsion. Finally, the microgel-in-oil mixture was drained into a large (12 mm diameter, approximately 1 mL volume) well, where the microgel particles were cured at 37 °C for a minimum of 1 h. The mixture was then extracted and purified by overlaying the oil solution on a buffered aqueous solution of HEPES-buffered saline (pH 7.4) and pelleting at 18,000 × g for 5 min in a tabletop centrifuge. The microgel-based pellet was washed in HEPES-buffered saline (pH 7.4) containing 10 mM CaCl2 and 0.01% w / v Pluronic F-127 (Sigma). The aqueous microgel solution was then allowed to swell and equilibrate with the buffer for at least 2 h at 37 °C.

[0100] To determine the operational regime of droplet splitting, device operation was monitored in real time using a high-speed camera (Phantom), followed by image analysis for size and polydispersity measurements (using ImageJ software) as well as splitting frequency (Phantom PC2). For stable droplet splitting on this platform, (i) all flows were started simultaneously (both water flows and both oil flows) at 5 μl / min until all air had flowed out of the device, (ii) the water flow rate was reduced to the desired overall volumetric rate (1.5-2 μL / min water flow rate and 1-5 μL / min oil flow rate) over 5 min, (iii) all accumulated liquid was aspirated from the collection well to ensure monodisperse μ-gels were collected, and (iv) the generation was performed.

[0101] Fully swollen and equilibrated "building block" microgel particles were pelleted by centrifugation at 18000xg for 5 min, and excess buffer (HEPES pH 7.4 + 10 mM CaCl2) was removed by aspiration and drying with cleanroom wipes. The microgel particles were then divided into aliquots each containing 50 μl of concentrated building block. Equal volumes of HEPES (pH 7.4) + 10 mM CaCl2 were added to the concentrated building block solutions. Half of these contained thrombin (Sigma) to a final concentration of 2 U / ml, and the other half contained FXIII (CSL Behring) to a final concentration of 10 U / ml. The solutions were then mixed thoroughly and spun down at 18000xg, followed by removal of excess liquid with cleanroom wipes (American Cleanstat).

[0102] Annealing was initiated by mixing equal volumes of building block solutions containing thrombin and FXIII with a positive displacement pipette (Gilson). The solutions were mixed thoroughly by repeated pipetting while simultaneously stirring with the pipette tip. The mixed solution was then pipetted into the desired site (mold, well plate, mouse wound, etc.).

[0103] To determine the gelation rate of each microgel, macroscale (50 μL) nonporous gels with the same chemical composition were generated. A 30 μL solution of 2X PEG-VS+ peptides (RGD, K, and Q peptides) dissolved in 0.3 M TEOA was mixed with 30 μL of 2X MMP-1 crosslinker dissolved in water. The mixture was vortexed quickly and 50 μL of the mixture was placed between two 8 mm rheological discs with a 1 mm gap (Anton Paar Physica MCR301 rheometer). The storage modulus was then measured (2.5 Hz, 0.1% strain) over a period of 20 min.

[0104] To determine the bulk storage modulus of the pre-annealed microgel particles and the annealed scaffolds, amplitude sweeps (0.01-10% strain) were performed to find the linear amplitude range for each. Amplitudes within the linear range were selected and frequency sweeps (0.5-5 Hz) were performed. For the pre-annealed microgel particles, 50 μL of microgel particles (5 wt% PEG-VS 4-arm MW=20 KDa, r=0.8 MMP-1 crosslinker, synthetic peptide concentrations of 250 μM synthetic K, 250 μM synthetic Q, 500 μM synthetic RGD) were injected between two 8 mm rheology discs with a spacing of 1 mm. For measurements of annealed scaffolds, 50 μL of microgel particles (N=3) (5 wt% PEG-VS 4-arm MW=20KDa, r=0.8 MMP-1 crosslinker, synthetic peptide concentrations of 250 μM synthetic K, 250 μM synthetic Q, 500 μM synthetic RGD) spiked with FXIIIa (5 U / mL final concentration) and thrombin (1 U / mL final concentration) were first pipetted between two glass slides. The mixture was allowed to partially anneal for 10 min, after which the top glass slide was removed and placed in a humidified incubator at 37 °C for 90 min. The scaffolds were then placed in HEPES-buffered saline (pH 7.4) overnight to equilibrate. The samples were then placed between two 8 mm disks on the rheometer and tested similarly to the unannealed microgel particles.

[0105] To determine the median pore size of the annealed microgel scaffolds, three separate scaffolds from each were annealed as described above using stock solutions of microgel particles of various sizes (total of nine scaffolds). Individual slices were taken for each gel (10 slices per gel, total of 30 slices for each gel type) with 50 μm between each slice using a Nikon Ti eclipse equipped with a C2 laser LED confocal. These images were then analyzed using a custom script written in MATLAB® to identify the pore area and to determine the size of each pore in px. 2 Each pore size was then used to calculate the median pore size of the gel, and converted to μm using the pixel μm conversion from the original microscopic image (0.31 μm / px). 2These areas were then converted to characteristic length measurements by squeezing the areas into circles and calculating the characteristic diameters of these circles. In the 30 μm microgel particles, the average pore size was about 12 μm. In the 100 μm microgel particles, the average pore size was about 19 μm. In the 150 μm microgel particles, the average pore size was about 37 μm. Note that the gaps or voids are continuous and do not resemble the well-defined spherical open areas connected by circular pores produced through microparticle leaching or inverse opal gel fabrication methods. However, the pore size reference is useful to simply describe the length scale of the voids.

[0106] To determine whether the microgel particles were covalently attached after the addition of FXIIIa, the scaffolds were directly visualized using SEM. The microgel particle mixture was treated with FXIIIa (10 U / ml) or buffer alone. The building block solution was then placed on a 1×1 in silicon wafer piece and visualized in a SEM (Hitachi S4700) high vacuum chamber (1×10 -3 The building blocks with and without FXIIIa were then visualized using 10 kV (max 10 mA) at 200× or 500×, as shown in FIG. 9D and FIG. 9F.

[0107] HEK293T cells, constitutively expressing GFP via lentiviral transfection, were maintained in DMEM (Life Technologies) supplemented with 10 μg / ml puromycin. Three cell lines were used for in vitro experiments: human dermal fibroblasts (HDF, Life Technologies), bone marrow-derived human mesenchymal stem cells (BMhMSC, Life Technologies), and adipose-derived human mesenchymal stem cells (AhMSC, Life Technologies). All cell lines were maintained according to the manufacturer's specifications (before and after incorporation into porous or non-porous gels). Specifically, for the MSC population, sternness was maintained using serum-reduced basal medium (Life Technologies).

[0108] For quantification of cell proliferation and visualization of network formation within porous scaffolds in vitro, particle-based scaffolds were annealed with microgel particles as described above, and a cell suspension was added to the building block solution prior to annealing. For each cell line, the cell suspension was cultured at 25 × 10 6 A final concentration of cells / ml was prepared. 2 μl of the cell suspension was then added to 50 μl of the FXIII-containing microgel particle mixture and mixed with 50 μl of the thrombin-containing microgel particle mixture (500 cells / μl gel). This mixture was injected into the corner of a coverslip-bottomed PDMS well. The top of the well was covered with a second coverslip, and the μgel / cell mixture was allowed to anneal at 37°C for 90 min.

[0109] After annealing was complete, the top coverslip was removed and the appropriate complete medium was added to the PDMS wells. At day 0, 4% PFA was added directly to the PDMS wells and fixed overnight at 4°C. Other cells were grown at 37°C with 5% CO2 for the indicated times (2, 4, and 6 days), at which point the cells were washed once with 1x PBS and fixed with 4% PFA overnight at 4°C. HEK-293-T cells were incorporated into star-shaped molds by mixing the cells with the microgel particles (as above) and pipetting 5 μl of the mixture into the corner of the mold. Immediately after, the microgel particles without the cells were pipetted into the remainder of the mold and annealed as above.

[0110] After 0, 2, 4, and 6 days of in vitro culture, proliferation was assessed by counting the number of cell nuclei present within the particle-based scaffold constructs. Nuclei were stained with 2 μg / ml DAPI solution in 1×PBS for 2 hours and then visualized with a Nikon C2 using a 405 nm LED laser. Specifically, each scaffold was imaged by taking 55 z-slices with a total z-height of 150 μm and compressing every 5 slices into a maximum intensity projection (MIP) image. Nuclei in the MIP were counted and total cell numbers were counted using a custom MATLAB script. For each time point, z-stack images of three separate microgel scaffolds were analyzed, with each z-stack image measuring 1270×1270×150 μm. 3 The total volume was measured (or approximately 280 nL). Counting at 90 min gave a calculation of approximately 525 cells / μl gel, consistent with the experimental loading (500 cells / μl gel).

[0111] For visualization of cell network formation within microgel scaffolds in vitro, constructs were prepared, grown, and fixed as described above. Scaffolds were blocked with 1% BSA in 1x PBS for 1 h at room temperature, after which F-actin was stained with rhodamine B·phalloidin complex (Life Technologies) for 3 h at room temperature. Next, scaffolds were washed with 1% BSA in 1x PBS, and then counterstained with 2 μg / ml DAPI solution in 1x PBS for 1 h at room temperature. Imaging was performed similarly to proliferation imaging, except that a 40× magnification water immersion lens was used. The total height of the image stack was 130 μm, and the total number of slices was 260 (volume capture approx. 15 nL).

[0112] PEG-VS scaffolds (5 wt% PEG-VS 4-arm MW=20KDa, r=0.8 MMP-1 crosslinker, synthetic peptide concentrations 250 μM synthetic K [SEQ ID NO:1], 250 μM synthetic Q [SEQ ID NO:2], 500 μM synthetic RGD [SEQ ID NO:3]) were used to encapsulate cells (500 cells / μL). The cell lines used were the same as in the microgel scaffold experiments. Gels were allowed to form for 20 min (TEOA 0.3 M, pH 8.25) and then placed in the appropriate medium. Gels were fixed overnight at 4°C with PFA after the indicated time points (t=90 min, 2 days, 4 days, and 6 days), washed, and stored in PBS. Gels were stained similarly to the microgel scaffolds. All samples were stored at 4°C in PBS containing P / S if not imaged. Imaging was performed using a NIKON® C2 confocal exactly as in the microgel scaffold in vitro experiments.

[0113] CLR:SKH1-Hrhr mice (Charles River Laboratories) (N=6 per study) were anesthetized with isofluorane (1.5%, 10 min), after which the nails were clipped and an analgesic (buprenorphine, 60 μL per 20 g at 0.015 μg / μL) was injected. The skin was pulled back and identical circular wounds were made on the backs of the mice using a 4 mm biopsy punch. The wounds were protected on the exterior with a rubber splint with 7–8 stitches on the surrounding skin to prevent wound closure by contraction. A nonporous or porous hydrogel containing 10 U / ml FXIIIa was injected into the wound bed and allowed to gel for 10 min, after which the wound was covered with a stretchy gauze wrap to prevent interactions between the animals. Mice were then separated into individual cages. Analgesics were administered subcutaneously every 12 hours for the next 48 hours (for sacrifice on day 1, analgesics were administered once after surgery).

[0114] On day 1, mice (N=6) were sacrificed by an overdose of isofluorane followed by spinal dislocation. The skin on the back was removed using surgical scissors and the wound site was isolated with a 10 mm biopsy punch. The samples were immediately fixed in 4% formaldehyde at 4°C (overnight) and then transferred to ethanol and the samples were embedded in paraffin blocks. The blocks were then sectioned at 6 μm thickness using a microtome (Leica) and stained with hematoxylin and eosin (H&E). For quantification of cellular infiltration within the hydrogel and immune response around the hydrogel, a series of three random high power (40×) fields (HPF) were examined for each section. The samples were analyzed for cellular infiltration (>0.1 mm into the gel) by counting the total number of cells of any type within the injected hydrogel (N=5, sum of cells in three sections analyzed per wound). More than 95% of the cells infiltrating the gel were neutrophils. To measure the immune response, an average of three HPFs from different sections of the wounds was examined. For each wound type, the total number of leukocytes / HPF within 0.2 mm of the hydrogel at the wound edge was quantified and averaged. The leukocyte counts of each wound were compared to its bilateral control of the same animal, and the relative difference was recorded as a fraction of the total immune response of each animal. This comparison was possible because each animal had one wound injected with the microgel scaffold and one wound injected with the non-porous control.

[0115] To track wound closure, wounds were imaged daily. Each wound site was imaged using a high resolution camera (NIKON® COOLPIX®). The closure fraction was determined by comparing the pixel area of ​​the wound to the pixel area within the 10 mm central hole of the red rubber splint. For each mouse / scaffold type, the closure fraction was normalized to day 0 (Figure 7B).

[0116] On day 5, mice (N=6) were sacrificed and tissues harvested in the same manner as mice on day 1. Samples were immediately immersed in TISSUE-TEK® Optimal Cutting Temperature (OCT) fluid and frozen into solid blocks in liquid nitrogen. Blocks were then cryosectioned at 25 μm thickness using a cryostat microtome (Leica) and kept frozen until use. Sections were then fixed in paraformaldehyde for 30 min at room temperature, hydrated in PBS, and kept at 4°C until staining.

[0117] Slides containing tissue sections were blocked with 3% normal goat serum (NGS) in 1x PBS + 0.05% Tween-20 (PBST) or, for sections stained with anti-keratin-5 alone, were simultaneously blocked and permeabilized with 0.2% TRITON® X-100 in 3% NGS in 1x PBST. Sections were then washed with 3% NGS in 1x PBST. Primary antibody dilutions were prepared in 3% NGS in 1x PBST as follows:

[0118] Rat anti-mouse CD11b (BD Pharmingen) - 1:100

[0119] Rat anti-mouse PECAM-1 (BD Pharmingen) - 1:100

[0120] Rabbit anti-mouse NG2 (Millipore) - 1:100

[0121] Rabbit anti-mouse keratin 5 (Covance, Inc.) - 1:250

[0122] Sections were stained with primary antibodies overnight at 4°C and then washed with 3% NGS in 1x PBST. All secondary antibodies were prepared at a 1:100 dilution in 3% NGS in 1x PBST. Sections were incubated in secondary antibodies for 1 hour at room temperature and then washed with 1x PBST. Sections were counterstained with 2 μg / ml DAPI in 1x PBST for 30 minutes at room temperature. Sections were mounted in Antifade Gold mounting medium.

[0123] Confocal z-stack images from day 5 tissue sections from both non-porous and microgel scaffold tissue blocks were compressed into MIPs and separated into individual images corresponding to each laser channel (i.e., Gel, DAPI, CD11b). The gel channel image was used to trace the edge of the gel-tissue interface using Adobe illustrator. The width of this line extended 75 μm from the interface into both the tissue and gel (total thickness 150 μm). The new edge of this line was then used to trim away unwanted portions of the original DAPI and CD11b images, capturing only the area corresponding to + / - 75 μm from the tissue-gel interface. These images were then imported into ImageJ, overlaid, and the DAPI and CD11b channels were merged into a single image. This image was analyzed using the cell counter plugin in ImageJ to quantify both the total number of nuclei and the total number of CD11b+ cells. Finally, the fraction of nuclei with corresponding CD11b+ signal was reported for both tissue and gel.

[0124] FIG. 11 illustrates an example of a method for treating damaged tissue 102. FIG. 11 illustrates a wound site 100 formed in mammalian tissue 102. In operation 500, microgel particles 12 are delivered to the wound site 100 using a delivery device 110 (e.g., a tube as shown) containing therein a slurry of microgel particles 12 contained in an aqueous solution. The microgel particles 12 are then spread into and across the wound site 100 using an optional applicator 122, as shown in operation 510. The applicator 122 is also used to make the top exposed surface of the microgel particles 12 generally flush with the surface of the tissue 102. The applicator 122 may also be used to raise or elevate the top exposed surface of the microgel particles 12 relative to the surface of the tissue 102, which may provide more structure for cellular ingrowth and prevent collapse of the tissue interface after full healing. Next, as shown in operation 520, annealing of the microgel particles 12 is initiated to form a scaffold 10 comprised of annealed microgel particles 12. In this embodiment, a light source 124 in the form of a flashlight is used to irradiate the mixture of microgel particles 12, a photoinitiator (e.g., Eosin Y), and a free radical transfer agent (e.g., RGD peptide). Of course, other annealing modes as described herein may also be used. The annealing reaction shown in FIG. 11 results in the formation of a covalently stabilized scaffold 10 comprised of microgel particles 12 with internal voids. Cells 106 (as shown in FIG. 2C) from the surrounding tissue 102 then begin to infiltrate the spaces within the scaffold 10, proliferate, stimulate, and ultimately complete the healing process of the tissue 102. In one embodiment, after the annealing reaction, a dressing or wet dressing is optionally placed over the scaffold-filled wound to protect the wound from injury during the healing process. After a period of time, as shown in operation 530, the scaffold 10 degrades and the tissue 102 returns to a healed state.

[0125] To evaluate the ability of the porous gel scaffolds to support cell growth and network formation, an in vitro cell morphology and proliferation model was developed using three human cell lines: dermal fibroblasts (HDFs), adipose-derived mesenchymal stem cells (AhMSCs), and bone marrow-derived mesenchymal stem cells (BMhMSCs). Single cell suspensions were dynamically incorporated into the FXIIIa-annealed porous gel scaffolds. The three cell lines showed high cell viability (>93%, Figure 12B) after 24 h of culture in the porous gel scaffolds.

[0126] Cells incorporated into the porous gel scaffolds began to show a spread morphology 90 min after the start of annealing. After 2 days of culture, all observed cells in the porous gel scaffolds showed a fully spread morphology, which persisted through day 6. Importantly, extensive network formation was observed by day 2 in all cell lines. The cellular networks increased in size and complexity throughout the experiment. As shown in FIG. 12A, BMhMSCs were particularly noteworthy because their spreadable network formation and slower proliferation rate indicated that these cells were able to spread to extreme lengths and form highly interconnected cellular networks within the microporous scaffolds.

[0127] As shown in FIG. 13A, microgel particles 12 can be combined and mixed with a solution of live cells 106 prior to annealing to produce a microporous scaffold 10 containing live cells 106 present within a microporous network and distributed uniformly or non-uniformly within the macroscopic annealed gel scaffold 10.

[0128] The microgel particles 12 could be purified in an aqueous solution of isotonic cell culture medium for storage and, when used for gel formation, were annealed to each other via a non-standard amide bond between the K and Q peptides, mediated by activated factor XIIIa (FXIIIa), a naturally occurring enzyme involved in stabilizing blood clots. This enzyme-mediated annealing process allowed the incorporation of live cells 106 into the dynamically forming porous scaffold 10 containing an interconnected microporous network. After addition of FXIIIa, but prior to scaffold annealing, a slurry of microgel particles 12 could be delivered via syringe application (Figure 13A) and eventually solidified in the shape of the injected cavity, as shown in Figures 13B-E.

[0129] As shown in Figure 14A, microfluidic fabrication of microgel particles 12 allows for deterministic control over the size and generation frequency of the microgels. The pressure applied to the inlet of the microfluidic system 20 determines the frequency of microgel generation (Figure 14B). Furthermore, as shown in Figure 14C, porous microgel scaffolds 10 generated with different sizes of microgel particles 12 have different porosity characteristics, such as the median pore size within the network.

[0130] While embodiments have been shown and described, various modifications can be made without departing from the scope of the inventive concepts disclosed herein. Accordingly, the inventive subject matter described herein should not be limited, except as by the following claims, and their equivalents.

Claims

1. 1. A composition for the treatment of tissue, the composition comprising a covalently stabilized porous scaffold of microgel particles, the covalently stabilized porous scaffold of microgel particles comprising: (a) a plurality of flowable microgel particles, the plurality of flowable microgel particles comprising: (i) a crosslinked hydrogel polymer, the crosslinked hydrogel polymer comprising poly(ethylene glycol) (PEG), hyaluronic acid, or a combination thereof; (ii) one or more annealing components comprising an acrylate, a vinyl sulfone, or a maleimide; (iii) a diameter of 5 μm to 1,000 μm; (iv) a cell adhesion moiety comprising fibronectin (or a fragment thereof), collagen (or a fragment thereof), laminin (or a fragment thereof), an RGD peptide, or hyaluronic acid; a plurality of flowable microgel particles comprising: (b) an annealing agent, which when exposed to the plurality of flowable microgel particles, bonds adjacent plurality of flowable microgel particles together in a covalent annealing reaction upon physical contact between adjacent microgel particles to form a covalently stabilized porous scaffold of the microgel particles, the covalently stabilized porous scaffold of microgel particles comprising pores, the pores having a median pore size sufficient to integrate cells derived from the tissue. A composition comprising:

2. 2. The composition of claim 1, wherein the hyaluronic acid comprises one or more reactive groups.

3. 3. The composition of claim 2, wherein the one or more reactive groups comprises a thiol-containing molecule.

4. 10. The composition of claim 1, wherein the annealing agent is a nucleophilic group comprising a thiol, an amine, or an aminoxy.

5. 10. The composition of claim 1, wherein the covalently stabilized porous scaffold of the microgel particles has a void volume of between 10% and 50%.

6. 10. The composition of claim 1, wherein the plurality of flowable microgel particles of (a) are present in an aqueous solution at a volume fraction of 30-99%.

7. 10. The composition of claim 1, wherein the plurality of flowable microgel particles has a storage modulus of at least 10 Pa.

8. 10. The composition of claim 1, wherein the plurality of flowable microgel particles are capable of annealing in 30 minutes or less.

9. 2. The composition of claim 1, wherein the formation of pores in the covalently stabilized porous scaffold does not require degradation of the covalently stabilized porous scaffold.

10. 10. The composition of claim 1, wherein the composition is delivered to the tissue by injection.

11. 11. The composition of claim 10, wherein the plurality of flowable microgel particles and the annealing agent are formulated for simultaneous or sequential delivery to the tissue.

12. 2. The composition of claim 1, wherein the pores have an average pore size of from 12 μm to 37 μm.

13. 2. The composition of claim 1, wherein cells from the tissue are integrated into the pores within 48 hours of contact with the covalently stabilized porous scaffold.

14. 10. The composition of claim 1, wherein the tissue treatment comprises tissue bulking.

15. 15. The composition of claim 14, wherein the tissue bulking comprises amelioration of volume loss associated with aging, lipoatrophy, lipodystrophy, skin scarring, or superficial or deep wrinkles.

16. 15. The composition of claim 14, wherein said tissue bulking comprises improving tissue contour.

17. 15. The composition of claim 14, wherein the tissue filling comprises repair of a tissue defect.

18. 15. The composition of claim 14, wherein said tissue bulking comprises repair of tissue displacement.

19. 10. The composition of claim 1, wherein the crosslinked hydrogel polymer comprises a combination of PEG and hyaluronic acid.

20. 20. The composition of claim 19, wherein the hyaluronic acid comprises one or more reactive groups.

21. 21. The composition of claim 20, wherein the one or more reactive groups comprise a thiol-containing molecule.

22. 20. The composition of claim 19, wherein the annealing agent comprises a nucleophilic group comprising a thiol, an amine, or an aminoxy.

23. 10. The composition of claim 1, wherein the plurality of flowable microgel particles are spherical.

24. 1. A composition for the treatment of tissue, the composition comprising a covalently stabilized porous scaffold of microgel particles, the covalently stabilized porous scaffold of microgel particles comprising: (a) a plurality of flowable microgel particles, the plurality of flowable microgel particles comprising: (i) a crosslinked hydrogel polymer, the crosslinked hydrogel polymer comprising poly(ethylene glycol) (PEG) crosslinked by a crosslinking agent; (ii) one or more annealing components comprising an acrylate, a vinyl sulfone, or a maleimide; (iii) a diameter of 5 μm to 1,000 μm; (iv) a cell adhesion moiety comprising fibronectin (or a fragment thereof), collagen (or a fragment thereof), laminin (or a fragment thereof), an RGD peptide, or hyaluronic acid; a plurality of flowable microgel particles comprising: (b) an annealing agent, which when exposed to the plurality of flowable microgel particles, bonds adjacent plurality of flowable microgel particles together in a covalent annealing reaction upon physical contact between adjacent microgel particles to form a covalently stabilized porous scaffold of the microgel particles, the covalently stabilized porous scaffold of microgel particles comprising pores, the pores having a median pore size sufficient to integrate cells derived from the tissue. A composition comprising:

25. 25. The composition of claim 24, wherein the poly(ethylene glycol) (PEG) comprises a multiarm poly(ethylene glycol) (PEG) vinyl sulfone.

26. 25. The composition of claim 24, wherein the crosslinker comprises an (MMP)-degradable crosslinker.

27. 25. The composition of claim 24, wherein the annealing agent is a nucleophilic group comprising a thiol, an amine, or an aminoxy.

28. 25. The composition of claim 24, wherein the covalently stabilized porous scaffold of the microgel particles has a void volume of between 10% and 50%.

29. 25. The composition of claim 24, wherein the plurality of flowable microgel particles of (a) are present in an aqueous solution at a volume fraction of 30-99%.

30. 25. The composition of claim 24, wherein the plurality of flowable microgel particles has a storage modulus of at least 10 Pa.

31. 25. The composition of claim 24, wherein the plurality of flowable microgel particles are capable of annealing in 30 minutes or less.

32. 25. The composition of claim 24, wherein the formation of pores in the covalently stabilized porous scaffold does not require degradation of the covalently stabilized porous scaffold.

33. 25. The composition of claim 24, wherein the composition is delivered to the tissue by injection.

34. 34. The composition of claim 33, wherein the plurality of flowable microgel particles and the annealing agent are formulated for simultaneous or sequential delivery to the tissue.

35. 25. The composition of claim 24, wherein the pores have an average pore size of from 12 μm to 37 μm.

36. 25. The composition of claim 24, wherein cells from the tissue are integrated into the pores within 48 hours of contact with the covalently stabilized porous scaffold.

37. 25. The composition of claim 24, wherein the tissue treatment comprises tissue bulking.

38. 38. The composition of claim 37, wherein the tissue bulking comprises amelioration of volume loss associated with aging, lipoatrophy, lipodystrophy, skin scarring, or superficial or deep wrinkles.

39. 38. The composition of claim 37, wherein said tissue bulking comprises improving tissue contour.

40. 38. The composition of claim 37, wherein the tissue filling comprises repair of a tissue defect.

41. 38. The composition of claim 37, wherein said tissue bulking comprises repair of tissue displacement.

42. 25. The composition of claim 24, wherein the plurality of flowable microgel particles are spherical.

Citation Information

Patent Citations

  • Production of joined microgel particles and article treated therewith

    JP1997025303A

  • electroprocessed collagen

    JP2004523484A

  • Injectable pore-forming hydrogel for material-based cell therapy

    JP2013542777A

  • Method of producing hybrid polymer-inorganic materials

    US20060257485A1

  • Cell-Laden Hydrogels

    US20080193536A1